Setter body and method for forming the same

JP2026534059APending Publication Date: 2026-10-14ION STORAGE SYSTEMS INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2026515957
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-13
Filing Date
2024-09-10
Publication Date
2026-10-14

Smart Images

  • Figure 2026534059000001_ABST
    Figure 2026534059000001_ABST
Patent Text Reader

Abstract

In one embodiment, the present invention provides a setter body for sintering a solid electrolyte material. The setter body comprises a substrate and a coating. The substrate has a first surface, a second surface opposite the first surface, and an outer surface extending from the first surface to the second surface. The substrate contains nickel. The coating is disposed at least partially on the first surface of the substrate. The coating contains at least about 1 mole percent of lithium. Furthermore, the mole percent of lithium in the coating is greater than the mole percent of lithium in the substrate. Another embodiment provides a method for forming the setter body. A further embodiment provides a method for forming a sintered solid electrolyte material.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] Cross-reference of related applications This PCT application claims the benefits of U.S. Provisional Patent Application No. 63 / 582,272, filed on 13 September 2023. This document is incorporated herein by reference in its entirety.

[0002] The present invention relates to a setter body for sintering solid electrolyte materials, a method for forming the same, and a method for using the same. [Background technology]

[0003] Solid-state batteries typically contain one or more solid electrolyte materials. These solid electrolyte materials can function, for example, as separators. In other examples, the solid electrolyte material may be formed as two layers comprising a porous layer and a dense layer. In such examples, the porous layer is a host matrix for receiving the active anode material (e.g., lithium), and the dense layer is the separator. However, the fabrication of films containing layers of varying porosity (e.g., porous and dense layers) presents challenges. For example, during sintering, each layer may undergo different degrees of shrinkage, leading to partial warping and curling. For this reason, setter bodies are frequently implemented to restrain the solid electrolyte material during sintering.

[0004] Typically, the setter body comprises a substrate containing a ceramic material (e.g., alumina, zirconia, magnesium oxide (MgO), and doped or undoped lithium lanthanum zirconium oxide (LLZO) compositions). While such setter bodies can be used to achieve desirable partial flatness, there are drawbacks associated with their use. Specifically, setter bodies containing a ceramic material substrate may exhibit limited or no reusability and may react with or cause compositional changes to at least a portion of the solid electrolyte material (e.g., the surface or a portion of the surface). The use of such setter bodies may also result in undesirable interdiffusion. Furthermore, some setter bodies may adhere to the solid electrolyte material during processing.

[0005] Therefore, the need for an improved setter body still exists. [Overview of the project]

[0006] In one embodiment, the present invention provides a setter body for sintering a solid electrolyte material. The setter body includes a substrate and a coating. The substrate has a first surface, a second surface opposite the first surface, and an outer surface extending from the first surface to the second surface. The substrate contains nickel. The coating is disposed at least partially on the first surface of the substrate. The coating contains at least about 1 mole percent of lithium. Furthermore, the mole percent of lithium in the coating is greater than the mole percent of lithium in the substrate.

[0007] In some embodiments, the nickel in the substrate is nickel element, nickel oxide, nickel alloy, or any combination thereof. For example, the substrate may contain nickel element. In some embodiments, the substrate may also contain a nickel alloy.

[0008] In some embodiments, the substrate includes a nickel alloy. For example, the nickel alloy may include aluminum, iron, copper, molybdenum, chromium, cobalt, tungsten, platinum, or any combination thereof.

[0009] In some embodiments, the substrate is a plate, a foam, or a mesh. For example, the substrate may be a plate. In some embodiments, the plate has a thickness of about 1,000 μm to about 10,000 μm. Also, in some embodiments, the plate has an apparent porosity of less than about 5%.

[0010] In other embodiments, the substrate is a foam. In some embodiments, the foam has a thickness of about 1 μm to about 1,000 μm. In some embodiments, the foam has an apparent porosity of more than about 50%. Also, in some embodiments, the foam has an apparent porosity of more than about 5%.

[0011] In other embodiments, the substrate is a mesh. In some embodiments, the mesh has a thickness of about 1 μm to about 1,000 μm. In some embodiments, the mesh has an apparent porosity of more than about 5%. Also, in some embodiments, the mesh has an apparent porosity of more than about 50%.

[0012] In some embodiments, the substrate is approximately 0.01 g / cm³ 2 ~Approx. 14.0g / cm 2 It has a weight-to-area ratio of approximately 0.1 g / cm². In other embodiments, the substrate has a weight-to-area ratio of approximately 0.1 g / cm². 2 ~about 0.5g / cm 2 It has a weight-to-area ratio of approximately 0.1 g / cm². In some embodiments, the substrate has a weight-to-area ratio of approximately 0.1 g / cm². 2 ~about 0.2g / cm 2 It has a weight-to-area ratio.

[0013] In some embodiments, the coating has a thickness of about 1 nm to about 100 μm. In other embodiments, the coating has a thickness of about 1 nm to about 1 μm.

[0014] In some embodiments, the coating comprises lithium element, lithium oxide, lithium alloy, or any combination thereof. For example, the coating may contain lithium element. In other embodiments, the coating comprises lithium oxide. Also, in some embodiments, the coating comprises lithium alloy.

[0015] In some embodiments, the coating includes at least one nodule extending away from the first surface of the substrate. In other embodiments, the at least one nodule includes aluminum, silicon, magnesium, titanium, calcium, oxygen, or any combination thereof.

[0016] In some embodiments, the substrate contains less than about 1 mole percent of lithium. In other embodiments, the substrate contains less than about 0.5 mole percent of lithium. Also, in some embodiments, the substrate does not contain lithium.

[0017] In some embodiments, the coating contains at least about 5 mole percent lithium. In other embodiments, the coating is at least partially disposed on at least one of the second surface and the outer surface of the substrate. For example, the coating is at least partially disposed on the second surface of the substrate. In some embodiments, the coating is at least partially disposed on the second surface of the substrate. Also, in some embodiments, the coating is at least partially disposed on the second surface and the outer surface of the substrate.

[0018] In another embodiment, the present invention relates to a method for forming a setter body, (a) Placing a substrate in a heating chamber, wherein the substrate has a first surface, a second surface opposite to the first surface, and an outer surface extending from the first surface to the second surface, and the substrate contains nickel. (b) providing a lithium source in the heating chamber, and (c) A method is provided which includes heating a heating chamber to a temperature of about 600°C to about 1,500°C to form a coating on the first surface of a substrate that contains at least partially lithium from a lithium source, thereby forming a setter body.

[0019] In some embodiments, the nickel in the substrate is nickel element, nickel oxide, nickel alloy, or any combination thereof. For example, the substrate contains nickel element. In other examples, the substrate contains a nickel alloy (e.g., a Ni alloy containing 20% ​​or less iron). In some examples, the nickel alloy contains aluminum, iron (e.g., 20% or less), copper, molybdenum, chromium, titanium, cobalt, tungsten, or any combination thereof.

[0020] In some embodiments, the substrate is a plate, foam, or mesh.

[0021] In some embodiments, the lithium source includes lithium lanthanum zirconium oxide (LLZO). In some of these embodiments, the LLZO is doped. In alternative embodiments, the LLZO is undoped.

[0022] In some embodiments, the substrate contains less than about 0.5 mole percent of lithium.

[0023] In some embodiments, the substrate does not contain lithium.

[0024] In some embodiments, the coating contains at least about 1 mole percent of lithium.

[0025] In some embodiments, the coating contains at least about 5 mole percent of lithium.

[0026] In some embodiments, the coating is at least partially located on at least one of the second surface and the outer surface of the substrate.

[0027] Some embodiments further include (d) introducing a gas into the heating chamber.

[0028] In some embodiments, the gas comprises a mixture of hydrogen and an inert gas. In other embodiments, the gas comprises a mixture of CO and an inert gas.

[0029] In some embodiments, the gas is introduced into the heating chamber at a flow rate of approximately 1 SCCM to approximately 3,000 SCCM.

[0030] In some embodiments, step (d) is carried out at least partially during step (c).

[0031] In some embodiments, the atmosphere inside the heating chamber during step (c) includes carbon monoxide, carbon dioxide, ammonia, hydrogen sulfide, methane, hydrogen, nitrogen, argon, helium, or any combination thereof.

[0032] In some embodiments, the method further comprises repeating step (c), the method according to any one of claims 30 to 48.

[0033] In some embodiments, the lithium source is a first lithium source, and the method is (e-1) After step (c), replace the first lithium source in the heating chamber with the second lithium source, and (e-2) Further includes repeating step (c).

[0034] In some embodiments, the method further includes cooling the heating chamber before step (e-1).

[0035] In a further embodiment, the present invention relates to a method for forming a sintered solid electrolyte material, (aa) Placing the setter body according to any one of claims 1 to 29 in the heating chamber, (bb) Placing a green body in a setter body coating, wherein the green body includes a solid electrolyte material. The present invention provides a method comprising heating a heating chamber to a temperature of approximately 600°C to approximately 1,500°C to form a sintered solid electrolyte, wherein the solid electrolyte material loses less than approximately 20 mole percent of lithium in step (cc).

[0036] In some embodiments, the solid electrolyte material loses less than approximately 15 mole percent of lithium during the step (cc).

[0037] In some embodiments, the solid electrolyte material loses less than approximately 10 mole percent of lithium during the step (cc).

[0038] In some embodiments, the method further includes introducing (dd) gas into the heating chamber.

[0039] In some embodiments, the gas comprises a mixture of hydrogen and an inert gas.

[0040] In some embodiments, the gas is introduced into the heating chamber at a flow rate of approximately 1 SCCM to approximately 3,000 SCCM.

[0041] In some embodiments, step (dd) is performed at least partially during step (cc).

[0042] In some embodiments, the atmosphere inside the heating chamber between steps (cc) includes carbon monoxide, carbon dioxide, ammonia, hydrogen sulfide, methane, hydrogen, nitrogen, argon, helium, or any combination thereof.

[0043] In some embodiments, the atmospheric pressure inside the heating chamber between steps (cc) is approximately 1 Pa to approximately 10 MPa.

[0044] In some embodiments, the green body further comprises at least one of a pore-forming agent and a binder, and step (cc) is (cc-1) Heat the heating chamber to a first temperature of approximately 400°C to approximately 800°C to burn at least one of the pore-forming agent and the binder, and (cc-2) Heating the heating chamber to a second temperature of approximately 600°C to approximately 1,500°C to form a sintered solid electrolyte, further comprising heating such that the second temperature is higher than the first temperature.

[0045] In some embodiments, the method further includes introducing (dd) gas into the heating chamber.

[0046] In some embodiments, step (dd) is: (dd-1) During step (cc-1), at least partially, the first gas is introduced into the heating chamber, and (dd-2) Further includes introducing at least partially the second gas into the heating chamber during step (cc-2).

[0047] In some embodiments, the first and second gases are each independently introduced into the heating chamber at flow rates of approximately 1 SCCM to approximately 3,000 SCCM.

[0048] In some embodiments, the first gas includes oxygen or air, and the second gas includes a mixture of hydrogen and an inert gas.

[0049] The following diagrams are provided as examples only and are not intended to limit the scope of the claimed invention. [Brief explanation of the drawing]

[0050] [Figure 1] This is a cross-sectional view of a first exemplary embodiment of a setter body for sintering solid electrolyte materials.

[0051] [Figure 2] This is a cross-sectional view of a second exemplary embodiment of a setter body for sintering solid electrolyte materials.

[0052] [Figure 3] This is a cross-sectional view of a third exemplary embodiment of a setter body for sintering solid electrolyte materials.

[0053] [Figure 4] This is a cross-sectional view of a fourth exemplary embodiment of a setter body for sintering solid electrolyte materials.

[0054] [Figure 5] This is a flowchart of a method for forming a setter body according to one embodiment of the present invention.

[0055] [Figure 6] This is a flowchart of a method for forming a sintered solid electrolyte material according to one embodiment of the present invention.

[0056] [Figure 7A] This is an image of the nickel mesh substrate from Example 1 before cleaning.

[0057] [Figure 7B] This is an image of the nickel mesh substrate from Example 1 after cleaning.

[0058] [Figure 8] This is a front view of the stack for forming the setter body according to Example 1.

[0059] [Figure 9] This is an image of a part of the nickel mesh substrate and setter body including knots according to Example 1.

[0060] [Figure 10] This graph shows the results of the XPS analysis of the setter body containing nickel plates according to Example 1, with the concentrations of nickel, lithium, oxygen, and carbon atoms plotted against the scanning depth of the setter body.

[0061] [Figure 11]This is a front view of the stack for sintering the solid electrolyte material according to Example 2.

[0062] [Figure 12A] These are images of the setter body and green tape of Example 2 before sintering.

[0063] [Figure 12B] This is an image of the setter body of Example 2 after sintering, and shows a cross-section of the obtained two-layer LLZO solid electrolyte material.

[0064] [Figure 12C] This is an image of the setter body from Example 2 after it has been recycled for use in six sintering cycles, and a cross-section of the two-layer LLZO solid electrolyte material obtained from the sixth sintering cycle.

[0065] [Figure 12D] This is an image of the setter body from Example 2 after it has been recycled for use in 11 sintering cycles, and a cross-section of the two-layer LLZO solid electrolyte material obtained from the eleventh sintering cycle.

[0066] [Figure 13A] This is a cross-sectional image of the LLZO bilayer material of Example 3 after processing in the sintering process.

[0067] [Figure 13B] This is the EDX spectrum of the dense surface of the LLZO bilayer material treated by the sintering process in an iron setter according to Example 3.

[0068] [Figure 14] This is a cross-sectional image of the LLZO bilayer material of Example 6 after processing in the sintering process. [Modes for carrying out the invention]

[0069] In each figure, the same reference number indicates the same element. For example, the substrate may be referred to as 102 in Figure 1, 302 in Figure 3, and 802a and 802b in Figure 8.

[0070] The present invention provides a setter body, a method for forming such a setter body, and a method for using such a setter body.

[0071] As used herein, unless otherwise specified, the following definitions shall apply:

[0072] I. Definition

[0073] The terms used herein are used solely to describe specific exemplary configurations and are not intended to be limiting. Where used herein, the singular articles “a,” “an,” and “the” may also include the plural unless otherwise clearly indicated in the context. The terms “comprises,” “comprising,” “including,” and “have” are comprehensive and thus indicate the presence of features, steps, operations, elements, and / or components, but do not exclude the presence or addition of one or more other features, steps, operations, elements, components, and / or groups thereof. The steps, processes, and operations of the methods described herein should not be construed as necessarily requiring their execution in a specific order described or illustrated unless specifically noted as such. Additional or alternative steps may be used.

[0074] In this specification, terms such as first, second, third, etc., may be used to describe various elements, components, areas, layers, and / or sections. These elements, components, areas, layers, and / or sections should not be limited by these terms. These terms may be used only to distinguish one element, component, area, layer, or section from another area, layer, or section. Terms such as "first," "second," etc., and other numerical terms do not imply arrangement or order unless explicitly indicated by the context. Thus, the first element, component, area, layer, or section described below may be called the second element, component, area, layer, or section without deviating from the teaching of the illustrated configuration.

[0075] In this specification, when an element is described as “on,” “engaged to,” “connected to,” “attached to,” or “joined to” another element, that element may be directly on, engaged to, connected to, attached to, or joined to the other element, or there may be an intervening element. On the other hand, when an element is described as “directly adjacent to,” “directly engaged to,” “directly connected to,” “directly attached to,” or “directly joined to” another element, it means that there is no intervening element or layer. Other words used to describe the relationship between elements should be interpreted similarly (e.g., “between” and “directly between,” “adjacent” and “directly adjacent,” etc.). As used herein, the term “and / or” includes any combination of one or more of the listed related items.

[0076] As used herein, the term “setter body” refers to a body comprising a substrate and a coating. The substrate has a first surface, a second surface opposite the first surface, and an outer surface extending from the first surface to the second surface. The substrate contains nickel. The coating is disposed at least partially on the first surface of the substrate. In some embodiments, the coating contains at least about 1 mole percent of lithium. In other embodiments, the coating contains at least about 1 wt% of lithium based on the total weight of the coating.

[0077] As used herein, the term “mol percent (mol%)” of a component (or element) indicates the proportion of a component (or element) present in an article (e.g., a substrate or coating) based on the total amount of all components, expressed in moles, present in the article. For example, with respect to the amount of lithium present in a coating, the mole percent of lithium is calculated according to the following formula:

number

[0078] It should be understood that the mole percentage of lithium in the coating and / or substrate includes elemental lithium in addition to lithium covalently and / or ionically bonded in lithium-containing compounds present in the coating and / or substrate. Lithium-containing compounds include lithium oxides and lithium alloys.

[0079] When used herein, “weight percent of lithium” in a coating and / or substrate should be understood to include elemental lithium in addition to lithium covalently and / or ionically bonded in lithium-containing compounds present in the coating and / or substrate.

[0080] As used herein, the term "solid electrolyte material" refers to materials suitable for use in solid-state battery cells, such as LLZO materials.

[0081] As used herein, the term "green body" refers to an unsintered body (e.g., a tape and / or film) that includes a solid electrolyte material.

[0082] As used herein, the term "apparent porosity" refers to the open (or accessible) porosity (i.e., the porosity excluding the volume(s) of sealed or closed pores, cells, or voids). Apparent porosity can be expressed as the ratio or percentage of the volume of open pores, cells, or voids to the total volume.

[0083] As used herein, the term "doped" and other forms of this word (e.g., "doping") refer to the presence or arrangement of atoms other than the base atoms in the crystal structure of a garnet material. For example, in the base structure of Li7La3Zr2O 12 (LLZO material), atoms may be substituted for part or all of lithium, part or all of lanthanum, part or all of zirconium, and / or part or all of oxygen. Such substitution may be performed after the base structure is formed or during the formation of the base structure. Similar substitutions can be made for other garnet-type structures.

[0084] As used herein, the term "powder bed" refers to a lithium-containing powder that is located proximate to a component being heat-treated. The powder may be composed of undoped LLZO, doped LLZO, or another material containing lithium. The powder bed can function as a lithium source during heat treatment.

[0085] II. Setter body

[0086] In one embodiment, the present invention provides a setter body for sintering a solid electrolyte material. As shown in Figure 1, the setter body 100 comprises a substrate 102 and a coating 104.

[0087] A. Circuit board

[0088] Referring to Figure 1, the substrate has a first surface 106, a second surface 108 opposite the first surface, and an outer surface 110 extending from the first surface to the second surface.

[0089] A suitable substrate material for the present invention does not substantially deplete the lithium of the SSE material (e.g., LLZO material) when such an SSE material is sintered, and does not adhere to the SSE material (e.g., LLZO material) during or after sintering.

[0090] Metal oxides and other oxide materials react with lithium-containing materials (e.g., SSE materials (e.g., LLZO materials)) under sintering conditions (e.g., high temperatures of approximately 600°C to 900°C). This undesirable reaction consumes lithium and can lead to lithium depletion from the SSE material. The reaction can also cause the SSE material to adhere to or fuse with the setter. Furthermore, the sintering process may promote undesirable interdiffusion of chemical species between the oxide material and the SSE material.

[0091] Metals and metal alloys generally have a natural metal oxide coating formed by exposure of the metal or alloy to atmospheric conditions. Metals and metal alloys with a natural metal oxide coating react with lithium-containing materials (e.g., SSE materials (e.g., LLZO materials)) unless the natural oxide coating is substantially or completely removed. Therefore, suitable metals and metal alloys useful for the substrates of the present invention are those in which the oxygen in the natural metal oxide coating can be substantially or completely removed when heated under reducing conditions (e.g., heating at a high temperature of about 600°C to about 900°C in an atmosphere containing hydrogen, carbon monoxide, or a combination thereof, or heating at a high temperature of about 600°C to about 900°C to bring the metal and / or metal alloy into contact with solid carbon).

[0092] In some embodiments, the natural oxide coating can be removed by heating the substrate material in a reducing environment (e.g., at a temperature of about 600°C to about 900°C) using, for example, an atmosphere containing hydrogen or carbon monoxide, or by using solid carbon in contact with the metal. In some examples, the material is heated at a temperature of about 600°C to about 900°C in an atmosphere of about 0.3% H2 to about 0.9% H2 in argon (or other inert gas) to remove all or substantially all of the natural metal oxide coating.

[0093] An Ellingham diagram is a plot of Gibbs free energy (ΔG) versus temperature. Since entropy (ΔH) and enthalpy (ΔS) are essentially constant with respect to temperature unless a phase change occurs, the free energy versus temperature plot is drawn as a series of straight lines, where ΔS is the slope and ΔH is the y-intercept. The slope of the line changes when any of the materials involved melt or evaporate. Because the free energy formed for most metal oxides is negative, the diagram is drawn with ΔG=O at the top of the figure, and all ΔG values ​​shown are negative numbers. The temperature at which a metal or oxide melts or evaporates can be marked on the diagram. In an Ellingham diagram of a metal reacting to form an oxide, the oxygen partial pressure is interpreted as 1 atmosphere, and the entire reaction is normalized to consume 1 mole of O2. Thus, an Ellingham diagram of a metal shows that a metal can reduce its natural oxide coating at temperatures of approximately 600° to 900°C. For example, in the Ellingham diagram, the free energy for the formation of nickel(II) oxide from nickel metal and oxygen is depicted by a line that slopes upward with increasing temperature. The line showing the free energy for the formation of water from hydrogen and oxygen is also a line that slopes upward with increasing temperature and is below the line from nickel to nickel dioxide. This indicates that, more preferably, water is thermodynamically formed at temperatures of about 600°C to about 900°C, and thus the natural oxide can be reduced to metallic nickel using hydrogen. Therefore, nickel is a suitable substrate. Similarly, other metals whose lines in the Ellingham diagram are above the hydrogen line in this temperature range (i.e., at temperatures of about 600°C to about 900°C) would also be suitable substrates. For example, cobalt, copper, and their alloys are also suitable substrates. However, since the line for iron is below the line for hydrogen, the natural oxide coating of iron is not removed at temperatures of about 600°C to about 900°C when hydrogen is used as a reducing agent. Therefore, as shown in Example 4 below, iron is not a suitable substrate. However, as shown in Examples 4 and 5 below, metal alloys formed with less than about 20% by weight of iron (e.g., less than about 15% by weight, less than about 10% by weight, or less than about 5% by weight) are suitable alloys.In Example 4, Invar (containing 64 wt% iron) did not form a suitable substrate, but in Example 5, Monel 400 (containing about 65 wt% Ni, about 33 wt% Cu, and about 2 wt% Fe) was shown to be a suitable substrate. As a result, alloys having at least about 80 wt% (e.g., about 80%-100%, about 85%-100%, about 90%-100%, or about 95%-100%) of one or more metals, where the straight line of the Ellingham diagram is above hydrogen in the temperature range of about 600°C to about 900°C, are suitable substrate materials. Table 1 describes specific examples of suitable substrate materials of the present invention.

[0094] [Table 1]

[0095] In some embodiments, the substrate contains nickel. In some embodiments, the nickel in the substrate is elemental nickel, nickel oxide, nickel alloy, or a combination thereof. For example, the substrate may contain elemental nickel. Also, in some embodiments, the substrate contains nickel oxide (e.g., nickel(II) oxide (NiO), nickel(III) oxide (Ni2O3), and other nickel-containing oxides).

[0096] In some embodiments, the substrate includes a nickel alloy. For example, the nickel alloy may include aluminum, iron, copper, molybdenum, chromium, titanium, cobalt, tungsten, platinum, or any combination thereof. In some embodiments, the nickel alloy includes aluminum. In some embodiments, the nickel alloy includes less than about 20% by weight (e.g., less than about 15% by weight, less than about 10% by weight, or less than about 5% by weight) of iron. For example, the Ni alloy includes about 0.01% to about 18% by weight (e.g., about 0.05% to about 15% by weight, about 0.05% to about 10% by weight, or about 0.05% to about 5% by weight) of Fe. In other embodiments, the nickel alloy includes copper. In some embodiments, the nickel alloy includes molybdenum. In some embodiments, the nickel alloy includes chromium. In other embodiments, the nickel alloy includes titanium. In some embodiments, the nickel alloy includes cobalt. In some embodiments, the nickel alloy includes tungsten. Also, in some embodiments, the nickel alloy includes copper and cobalt. Non-specific examples of nickel alloys include nickel alloy 400 (UNSN04400), alloy B-2 (UNSN10665), nichrome 70 (UNSN06008), nickel alloy 600 (UNSN06600), nickel alloy 601 (UNSN06601), nickel alloy X-750 (UNSN07750), nickel alloy 825 (UNSN08825), alloy G-3 (UNSN06985), nickel alloy 800 (U Examples include NSN08800), alloy C-276 (UNSN10276), alloy C-22 (UNSN06022), nickel alloy 59 (UNSN06059), alloy C-2000 (UNSN06200), nickel alloy 686 (UNSN06686), nickel alloy 617 (UNSN06617), nickel alloy HR-160 (UNSN12160), nickel alloy 602CA, and Nitinol (UNSN01555).

[0097] In some embodiments, the nickel alloy contains one or more inert metals. In other embodiments, the nickel alloy has a melting point of at least about 1,300°C. For example, the nickel alloy may have a melting point of at least about 1,400°C. In yet another embodiment, the nickel alloy has a melting point of at least about 1,500°C.

[0098] In some embodiments, the substrate is a plate, foam, or mesh. In other embodiments, the substrate is a plate. When the substrate is a plate, the plate may have a thickness of about 1 μm (e.g., if the plate of the substrate is foil) to about 10,000 μm. In some embodiments, the plate has a thickness of about 1,000 μm to about 10,000 μm. In some embodiments, the plate has a thickness of about 1,000 μm to about 2,000 μm. In other embodiments, the plate has a thickness of about 2,000 μm to about 3,000 μm. In some embodiments, the plate has a thickness of about 3,000 μm to about 4,000 μm. In some embodiments, the plate has a thickness of about 4,000 μm to about 5,000 μm. In other embodiments, the plate has a thickness of about 5,000 μm to about 6,000 μm. In some embodiments, the plate has a thickness of about 6,000 μm to about 7,000 μm. In some embodiments, the plate has a thickness of approximately 7,000 μm to approximately 8,000 μm. In other embodiments, the plate has a thickness of approximately 8,000 μm to approximately 9,000 μm. In some embodiments, the plate has a thickness of approximately 2,500 μm to approximately 7,500 μm. Also, in some embodiments, the plate has a thickness of approximately 9,000 μm to approximately 10,000 μm.

[0099] In some embodiments, the plate has an apparent porosity of less than about 5%. For example, the plate may have an apparent porosity of less than 2.5 percent. In other embodiments, the plate has an apparent porosity of less than about 1%. Also, in some embodiments, the plate is substantially pore-free (or pore-free).

[0100] In some embodiments, the plate includes cladding, which includes nickel element, nickel oxide, nickel alloy, or any combination thereof. For example, the plate includes a ceramic cladding having nickel element, nickel oxide, nickel alloy, or any combination thereof. In other examples, the plate includes a ceramic (e.g., aluminum oxide ceramic, zirconium oxide ceramic, or other ceramic) and cladding which includes nickel element, nickel oxide (such as any nickel oxide described herein), nickel alloy (such as any nickel alloy described herein), or any combination thereof. In other embodiments, the plate includes aluminum, iron, copper, tin, or any combination thereof and includes cladding which includes nickel element, nickel oxide, nickel alloy, or any combination thereof. For example, the plate includes copper with nickel cladding, iron with nickel cladding, tin with nickel cladding, or aluminum with nickel cladding.

[0101] In some embodiments, the plate comprises a nickel layer, the nickel layer comprising nickel element, nickel oxide, nickel alloy, or any combination thereof, and the nickel layer is deposited on the surface of the ceramic as an annealed paste by sputtering or vapor deposition. In some examples, the plate comprises a ceramic (e.g., aluminum oxide ceramic, zirconium oxide ceramic, or other ceramic) and a nickel layer, the nickel layer comprising nickel element, nickel oxide (e.g., any nickel oxide described herein), nickel alloy (e.g., any nickel alloy described herein), or any combination thereof, and the thickness of the nickel layer is at least about 50 μm.

[0102] In some embodiments, the substrate is a foam. When the substrate is a foam, the foam may have a thickness of about 1 μm to about 1,000 μm. For example, the foam may have a thickness of about 1 μm to about 100 μm. In other embodiments, the foam may have a thickness of about 100 μm to about 200 μm. In some embodiments, the foam may have a thickness of about 200 μm to about 300 μm. In some embodiments, the foam may have a thickness of about 300 μm to about 400 μm. In other embodiments, the foam may have a thickness of about 400 μm to about 500 μm. In some embodiments, the foam may have a thickness of about 500 μm to about 600 μm. In some embodiments, the foam may have a thickness of about 600 μm to about 700 μm. In other embodiments, the foam may have a thickness of about 700 μm to about 800 μm. In some embodiments, the foam may have a thickness of about 800 μm to about 900 μm. In some embodiments, the foam may have a thickness of approximately 250 μm to approximately 750 μm. In other embodiments, the foam may have a thickness of approximately 900 μm to approximately 1,000 μm.

[0103] In some embodiments, the foam has an apparent porosity of more than about 5%. For example, the foam may have an apparent porosity of more than about 10%. In other embodiments, the foam has an apparent porosity of more than about 20%. In some embodiments, the foam has an apparent porosity of more than about 30%. In some embodiments, the foam has an apparent porosity of more than about 40%. In other embodiments, the foam has an apparent porosity of more than about 50%. In some embodiments, the foam has an apparent porosity of more than about 60%. In some embodiments, the foam has an apparent porosity of more than about 70%. In other embodiments, the foam has an apparent porosity of more than about 80%. Also, in some embodiments, the foam has an apparent porosity of more than about 90%.

[0104] In some embodiments, the foam has an apparent porosity of about 20% to about 80%. In other embodiments, the foam has an apparent porosity of about 35% to about 75%. In some embodiments, the foam has an apparent porosity of about 45% to about 65%. In some embodiments, the foam has an apparent porosity of about 50% to about 60%. In some embodiments, the foam has an apparent porosity of about 60% to about 80%. In some embodiments, the foam has an apparent porosity of about 20% to about 95%. Also, in some embodiments, the foam has an apparent porosity of about 50% to about 90%.

[0105] In some embodiments, the substrate is a mesh. When the substrate is a mesh, the mesh may have a thickness of approximately 1 μm to approximately 1,000 μm. For example, the mesh may have a thickness of approximately 1 μm to approximately 100 μm. In other embodiments, the mesh may have a thickness of approximately 100 μm to approximately 200 μm. In some embodiments, the mesh may have a thickness of approximately 200 μm to approximately 300 μm. In some embodiments, the mesh may have a thickness of approximately 300 μm to approximately 400 μm. In other embodiments, the mesh may have a thickness of approximately 400 μm to approximately 500 μm. In some embodiments, the mesh may have a thickness of approximately 500 μm to approximately 600 μm. In some embodiments, the mesh may have a thickness of approximately 600 μm to approximately 700 μm. In other embodiments, the mesh may have a thickness of approximately 700 μm to approximately 800 μm. In some embodiments, the mesh may have a thickness of approximately 800 μm to approximately 900 μm. In some embodiments, the mesh may have a thickness of approximately 250 μm to approximately 750 μm. In other embodiments, the mesh may have a thickness of approximately 900 μm to approximately 1,000 μm.

[0106] In some embodiments, the mesh has an apparent porosity of more than about 5%. For example, the mesh may have an apparent porosity of more than about 10%. In other embodiments, the mesh has an apparent porosity of more than about 20%. In some embodiments, the mesh has an apparent porosity of more than about 30%. In some embodiments, the mesh has an apparent porosity of more than about 40%. In other embodiments, the mesh has an apparent porosity of more than about 50%. In some embodiments, the mesh has an apparent porosity of more than about 60%. In some embodiments, the mesh has an apparent porosity of more than about 70%. In other embodiments, the mesh has an apparent porosity of more than about 80%. Also, in some embodiments, the mesh has an apparent porosity of more than about 90%.

[0107] In some embodiments, the mesh has an apparent porosity of about 20% to about 80%. In other embodiments, the mesh has an apparent porosity of about 35% to about 75%. In some embodiments, the mesh has an apparent porosity of about 45% to about 65%. In some embodiments, the mesh has an apparent porosity of about 50% to about 60%. In some embodiments, the mesh has an apparent porosity of about 60% to about 80%. In some embodiments, the mesh has an apparent porosity of about 20% to about 95%. Also, in some embodiments, the mesh has an apparent porosity of about 50% to about 90%.

[0108] In some embodiments, the substrate (e.g., mesh) has a density of approximately 0.01 g / cm². 2 ~Approx. 14.0g / cm 2 The weight-to-area ratio (for example, approximately 0.05 g / cm²) 2 ~Approx. 1.0g / cm 2 ) has. For example, the substrate has a density of approximately 0.01 g / cm³. 2 ~about 0.5g / cm 2 It may have a weight-to-area ratio of approximately 0.1 g / cm². In some embodiments, the substrate has a weight-to-area ratio of approximately 0.1 g / cm². 2 ~about 0.5g / cm 2 It has a weight-to-area ratio of approximately 0.1 g / cm². In other embodiments, the substrate has a weight-to-area ratio of approximately 0.1 g / cm². 2 ~Approximately 0.4g / cm³2 It has a weight-to-area ratio of approximately 0.1 g / cm². In some embodiments, the substrate has a weight-to-area ratio of approximately 0.1 g / cm². 2 ~about 0.3g / cm 2 It has a weight-to-area ratio of approximately 0.1 g / cm². In some embodiments, the substrate has a weight-to-area ratio of approximately 0.1 g / cm². 2 ~about 0.2g / cm 2 It has a weight-to-area ratio.

[0109] In some embodiments, the substrate contains less than about 1 mole percent of lithium. In other embodiments, the substrate contains less than about 0.5 mole percent of lithium. In additional embodiments, the substrate contains less than about 0.25 mole percent (e.g., less than about 0.10 mole percent) of lithium. Also, in some embodiments, the substrate does not contain lithium.

[0110] B. Coating

[0111] When lithium-containing materials such as LLZO are sintered, they volatilize lithium, generating lithium vapor pressure at high temperatures. If the lithium vapor pressure immediately adjacent to the article being sintered does not reach an equilibrium or saturation point, the lithium-containing material (LLZO) will be depleted of lithium, which is undesirable for producing sintered SSE material. In the case of LLZO, lithium depletion before or during sintering can prevent the LLZO from becoming denser and leading to insufficient sintering, or it can produce undesirable secondary phases poor in lithium, such as La2Zr2O7. Lithium-containing materials, especially setter materials used with LLZO, adsorb lithium on their surface upon first use, acting as a lithium sink in the furnace and depleting lithium from the sintered product. By coating the substrate with a lithium-containing coating before sintering, the lithium vapor pressure immediately adjacent to the sintered product can reach an equilibrium point, reducing lithium depletion from the sintered product. The coating allows the setter to be used repeatedly and indefinitely.

[0112] Referring again to Figure 1, the coating is at least partially located on the first surface of the substrate. The coating contains at least about 1 mole percent of lithium. Also, the mole percent of lithium in the coating is greater than the mole percent of lithium in the substrate.

[0113] In some embodiments, as shown in Figure 1, the coating is applied to the entire first surface of the substrate. In other embodiments, the coating is applied to substantially the entire first surface of the substrate (e.g., at least 60%, at least 70%, at least 80%, at least 90%, or at least 95%). In yet another embodiment, the coating is applied to only a portion of the first surface of the substrate (e.g., about 10% to about 55% of the first surface of the substrate).

[0114] In some embodiments, the coating has a thickness of about 1 nm to about 100 μm. In some embodiments, the coating has a thickness of about 10 nm to about 100 nm (e.g., about 20 nm to about 75 nm). In other embodiments, the coating has a thickness of about 1 nm to about 50 μm. In some embodiments, the coating has a thickness of about 1 nm to about 1 μm. For example, the coating may have a thickness of about 1 nm to about 100 nm. In some embodiments, the coating has a thickness of about 100 nm to about 200 nm. In some embodiments, the coating has a thickness of about 200 nm to about 300 nm. In other embodiments, the coating has a thickness of about 300 nm to about 400 nm. In some embodiments, the coating has a thickness of about 400 nm to about 500 nm. In some embodiments, the coating has a thickness of about 500 nm to about 600 nm. In other embodiments, the coating has a thickness of about 600 nm to about 700 nm. In some embodiments, the coating has a thickness of about 700 nm to about 800 nm. In some embodiments, the coating has a thickness of approximately 800 nm to approximately 900 nm. In other embodiments, the coating has a thickness of approximately 250 nm to approximately 750 nm. Also, in some embodiments, the coating has a thickness of approximately 900 nm to approximately 1 μm.

[0115] In some embodiments, the coating includes lithium element, lithium oxide, lithium peroxide, lithium carbonate, lithium carbonate alloy, or any combination thereof. For example, the coating may include lithium element. In other embodiments, the coating includes an elemental oxide, peroxide, or hydroxide of lithium. In some embodiments, the coating includes lithium oxide. Also, in some embodiments, the coating includes a lithium alloy.

[0116] In some embodiments, the coating may include at least one knot extending away from the first surface of the substrate. In other embodiments, the coating includes one knot. Also, in some embodiments, the coating includes multiple knots.

[0117] If present, at least one nodule contains aluminum, silicon, magnesium, calcium, titanium, oxygen, or any combination thereof. For example, at least one nodule may contain aluminum. In other embodiments, at least one nodule contains silicon. In some embodiments, at least one nodule contains magnesium. In some embodiments, at least one nodule contains calcium. In some embodiments, at least one nodule contains oxygen (i.e., oxygen is present in the form of one or more oxides). Also, in some embodiments, at least one nodule contains aluminum, silicon, magnesium, calcium, and oxygen.

[0118] In some embodiments, the coating contains at least about 2.5 mol percent of lithium. In other embodiments, the coating contains at least about 5 mol percent of lithium. For example, the coating may contain at least about 10 mol percent of lithium. In other embodiments, the coating contains at least about 15 mol percent of lithium. In some embodiments, the coating contains at least about 20 mol percent of lithium. In some embodiments, the coating contains at least about 25 mol percent of lithium. In other embodiments, the coating contains at least about 30 mol percent of lithium. In some embodiments, the coating contains at least about 35 mol percent of lithium. In some embodiments, the coating contains at least about 40 mol percent of lithium. In other embodiments, the coating contains at least about 45 mol percent of lithium. In some embodiments, the coating contains at least about 50 mol percent of lithium. In some embodiments, the coating contains at least about 55 mol percent of lithium. In other embodiments, the coating contains at least about 60 mol percent of lithium. In some embodiments, the coating contains at least about 65 mol percent of lithium. In some embodiments, the coating contains at least about 70 mol percent of lithium. In other embodiments, the coating contains at least about 75 mol percent of lithium. In some embodiments, the coating also contains at least about 80 mole percent lithium.

[0119] In some embodiments, the coating contains at least about 1 wt% lithium based on the total weight of the coating. In other embodiments, the coating contains at least about 2.5 wt% lithium based on the total weight of the coating. For example, the coating contains at least about 5 wt% lithium based on the total weight of the coating. In some embodiments, the coating contains at least about 10 wt% lithium based on the total weight of the coating. In some embodiments, the coating contains at least about 15 wt% lithium based on the total weight of the coating. In other embodiments, the coating contains at least about 20 wt% lithium based on the total weight of the coating. In some embodiments, the coating contains at least about 25 wt% lithium based on the total weight of the coating. In some embodiments, the coating contains at least about 30 wt% lithium based on the total weight of the coating. In other embodiments, the coating contains at least about 35 wt% lithium based on the total weight of the coating. In some embodiments, the coating contains at least about 40 wt% lithium based on the total weight of the coating. In some embodiments, the coating contains at least about 45 wt% lithium based on the total weight of the coating. In other embodiments, the coating contains at least about 50 wt% lithium based on the total weight of the coating. In some embodiments, the coating contains at least about 55% by weight of lithium based on the total weight of the coating. In some embodiments, the coating contains at least about 60% by weight of lithium based on the total weight of the coating. In other embodiments, the coating contains at least about 65% by weight of lithium based on the total weight of the coating. In some embodiments, the coating contains at least about 70% by weight of lithium based on the total weight of the coating. In some embodiments, the coating contains at least about 75% by weight of lithium based on the total weight of the coating. Also, in some embodiments, the coating contains at least about 80% by weight of lithium based on the total weight of the coating.

[0120] In some embodiments, the coating is at least partially distributed on at least one of the second surface and outer surface of the substrate. For example, as shown in Figure 2, the coating 204 may be at least partially distributed on the outer surface 210 of the substrate 202. In the illustrated embodiment, the coating is distributed over the entire outer surface of the substrate. In other embodiments, the coating is distributed over substantially the entire outer surface of the substrate (e.g., at least 60%, at least 70%, at least 80%, at least 90%, or at least 95%). Also, in some embodiments, the coating is distributed over only a portion of the outer surface of the substrate.

[0121] Referring to Figure 3, in other embodiments, the coating 304 is at least partially distributed on the second surface 308 of the substrate 302. In some embodiments, the coating is distributed over the entire second surface of the substrate. In other embodiments, the coating is distributed over substantially the entire second surface of the substrate (e.g., at least 60%, at least 70%, at least 80%, at least 90%, or at least 95%). Also, in some embodiments, the coating is distributed over only a portion of the second surface of the substrate.

[0122] As shown in Figure 4, the coating 404 may be applied to the first surface, the second surface, and the outer surface of the substrate 402. In some embodiments, the coating is applied to the entire first surface, the second surface, and the outer surface of the substrate. In other embodiments, the coating is applied to substantially the entire first surface, the second surface, and the outer surface of the substrate (e.g., at least 60%, at least 70%, at least 80%, at least 90%, or at least 95%). Also in some embodiments, the coating is applied to only portions of the first surface, the second surface, and the outer surface of the substrate.

[0123] Referring to Figures 8 and 9, in some embodiments, if the substrate is a mesh or foam (not shown), the coating may be on one or more portions of the outer surface of the mesh or foam. For example, the coating may be placed substantially over the entire outer surface of the mesh substrate, so that each of the wires or filaments forming the mesh is substantially coated with the coating.

[0124] C. Alternative Implementations

[0125] In another embodiment, the present invention provides a sintering setter body for sintering a solid electrolyte material. The setter body comprises a substrate and a coating. The substrate has a first surface, a second surface opposite the first surface, and an outer surface extending from the first surface to the second surface. The substrate contains nickel. The coating is disposed at least partially on the first surface of the substrate. The coating contains at least about 1% by weight of lithium based on the total weight of the coating. Also, the weight percentage of lithium in the coating is greater than the weight percentage of lithium in the substrate.

[0126] In a further embodiment, the present invention provides a sintering setter body for sintering a solid electrolyte material. The setter body comprises a substrate and a coating. The substrate has a first surface, a second surface opposite the first surface, and an outer surface extending from the first surface to the second surface. The substrate further comprises a mesh containing nickel. The coating is disposed at least partially on the first surface of the mesh substrate. The coating contains at least about 5 mole percent of lithium (e.g., about 5 mole percent to about 50 mole percent). Also, the mole percent of lithium in the coating is greater than the mole percent of lithium in the substrate.

[0127] In yet another embodiment, the present invention provides a sintering setter body for sintering a solid electrolyte material. The setter body comprises a substrate and a coating. The substrate has a first surface, a second surface opposite the first surface, and an outer surface extending from the first surface to the second surface. The substrate contains nickel. The coating is disposed at least partially on two or more surfaces selected from the first surface, the second surface, and the outer surface of the substrate. The coating contains at least about 1 mole percent of lithium (e.g., about 5 mole percent to about 50 mole percent). Also, the mole percent of lithium in the coating is greater than the mole percent of lithium in the substrate.

[0128] In another embodiment, the present invention provides a sintering setter body for sintering a solid electrolyte material. The setter body comprises a substrate and a coating. The substrate has a first surface, a second surface opposite the first surface, and an outer surface extending from the first surface to the second surface. The substrate contains nickel. The coating is disposed at least partially on two or more surfaces selected from the first surface, the second surface, and the outer surface of the substrate. The coating contains at least about 5 mole percent of lithium (e.g., about 5 mole percent to about 50 mole percent). Also, the mole percent of lithium in the coating is greater than the mole percent of lithium in the substrate.

[0129] In another embodiment, the present invention provides a sintering setter body for sintering a solid electrolyte material. The setter body comprises a substrate and a coating. The substrate has a first surface, a second surface opposite the first surface, and an outer surface extending from the first surface to the second surface. The substrate contains nickel. The coating is at least partially disposed on two or more surfaces selected from the first surface, the second surface, and the outer surface of the substrate, and the coating is partially disposed between the first surface and the second surface (i.e., the coating is at least partially embedded in the substrate between the first surface and the second surface). The coating contains at least about 5 mole percent of lithium (e.g., about 5 mole percent to about 50 mole percent). Also, the mole percent of lithium in the coating is greater than the mole percent of lithium in the substrate.

[0130] In one embodiment, the present invention provides a setter body for sintering a solid electrolyte material. The setter body includes a substrate and a coating. The substrate has a first surface, a second surface opposite the first surface, and an outer surface extending from the first surface to the second surface. The substrate further includes a nickel-containing mesh. The substrate does not contain lithium. The coating is disposed at least partially on the first surface of the substrate. The coating contains at least about 5 mole percent of lithium. Also, the mole percent of lithium in the coating is greater than the mole percent of lithium in the substrate.

[0131] In one embodiment, the present invention provides a setter body for sintering a solid electrolyte material. The setter body includes a substrate and a coating. The substrate has a first surface, a second surface opposite the first surface, and an outer surface extending from the first surface to the second surface. The substrate further includes a mesh containing nickel. The coating is disposed at least partially on the first surface of the substrate and between the first surface and the second surface of the substrate. The coating contains at least about 5 mole percent of lithium (e.g., about 5 mole percent to about 50 mole percent). Also, the mole percent of lithium in the coating is greater than the mole percent of lithium in the substrate.

[0132] III. Method for forming setter bodies

[0133] Another aspect of the present invention provides a method for forming a setter body. Figure 5 is a flowchart illustrating an example of a method for forming a setter body, and referring thereto, the method is as follows: (a) Placing a substrate in a heating chamber, wherein the substrate has a first surface, a second surface opposite to the first surface, and an outer surface extending from the first surface to the second surface, and the substrate contains nickel (5002), (b) providing a lithium source in the heating chamber (5004), and (c) Heating the heating chamber to a temperature of approximately 600°C to approximately 1,500°C to form a coating on the first surface of the substrate that contains at least partially lithium from a lithium source, thereby forming a setter body (5006).

[0134] The substrate may be any of the substrates described herein. For example, in some embodiments, the nickel of the substrate is nickel element, nickel oxide, nickel alloy, or any combination thereof. In other embodiments, the substrate includes nickel cladding (e.g., copper with nickel cladding, iron with nickel cladding, tin with nickel cladding, or aluminum with nickel cladding). In other embodiments, the substrate includes nickel element. In some embodiments, the substrate includes nickel alloy. Also in some embodiments, the nickel alloy includes aluminum, iron, copper, molybdenum, chromium, titanium, cobalt, tungsten, or any combination thereof.

[0135] In some embodiments, the substrate is a plate, a foam, or a mesh. For example, the substrate may be a plate. In other embodiments, the substrate is a foam. Also, in some embodiments, the substrate is a mesh.

[0136] In some embodiments, the substrate contains less than about 1 mole percent of lithium. In other embodiments, the substrate contains less than about 0.5 mole percent of lithium. Also, in some examples and embodiments, the substrate does not contain lithium.

[0137] In some embodiments, step (a) may include placing multiple substrates in the heating chamber. For example, step (a) may include processing 2, 5, 10, 20, or more substrates in the heating chamber. In some embodiments, the multiple substrates may be placed in the heating chamber as a stack of substrates.

[0138] In some embodiments, the heating chamber is an oven or a furnace.

[0139] In some embodiments, the lithium source comprises lithium lanthanum zirconium oxide (LLZO). For example, in some embodiments, the lithium source may be provided as a powder bed containing LLZO. When the lithium source comprises LLZO, the LLZO may be doped, undoped, or a mixture of doped and undoped LLZO. In some embodiments, the LLZO is doped. In other embodiments, the LLZO is undoped. Also, in some embodiments, the lithium source comprises residual lithium remaining in the heating chamber from a previous iteration of the method. In some embodiments, the lithium source comprises lithium metal, lithium oxide, lithium hydroxide, lithium halogen salt, lithium carbonate, lithium nitrate, or any combination thereof. For example, the lithium source comprises Li2O, LiOH, LiOH·H2O, LiCl, Li2CO3, LiNO3, or any combination thereof. In some embodiments, the lithium source comprises LiO2. In some embodiments, the lithium source comprises LiOH. In other embodiments, the lithium source comprises LiOH·H2O. In some embodiments, the lithium source includes LiCl. In some embodiments, the lithium source includes Li2CO3. In some embodiments, the lithium source includes LiNO3.

[0140] In some embodiments, the lithium source includes or is provided with a powder bed, sacrificial tape, furnace method artifacts, or any combination thereof.

[0141] In some embodiments, step (c) includes heating the heating chamber to a temperature of about 700°C to about 1,500°C. In other embodiments, step (c) includes heating the heating chamber to a temperature of about 800°C to about 1,500°C (e.g., about 800°C to about 1,200°C). In some embodiments, step (c) includes heating the heating chamber to a temperature of about 900°C to about 1,500°C. In some embodiments, step (c) also includes heating the heating chamber to a temperature of about 1,000°C to about 1,500°C.

[0142] In some embodiments, the coating contains at least about 1 mole percent of lithium. In other embodiments, the coating contains at least about 5 mole percent of lithium. In some embodiments, the coating contains at least about 1 wt% of lithium based on the total weight of the coating. Also in some embodiments, the coating contains at least about 5 wt% of lithium based on the total weight of the coating.

[0143] In some embodiments, the coating is at least partially disposed on at least one of the second surface and outer surface of the substrate. In other embodiments, the coating is at least partially disposed on the second surface of the substrate. In some embodiments, the coating is at least partially disposed on the outer surface of the substrate. Also, in some embodiments, the coating is at least partially disposed on the second surface and outer surface of the substrate.

[0144] In some embodiments, step (c) is performed for at least about 1 minute. In other embodiments, step (c) is performed for at least about 1 hour (e.g., about 1 hour to about 3 hours, about 1.5 hours to about 2.5 hours, or about 2 hours). In some embodiments, step (c) is performed for at least about 2 hours. Also, in some embodiments, step (c) is performed for between about 1 minute and about 5 hours.

[0145] In some embodiments, the method is (d) Further including introducing gas into the heating chamber.

[0146] In some embodiments, the gas includes carbon monoxide, carbon dioxide, ammonia, hydrogen sulfide, methane, hydrogen, nitrogen, argon, helium, or any combination thereof. In other embodiments, the gas includes a mixture of hydrogen and an inert gas (e.g., nitrogen). For example, the gas may include carbon monoxide. In some embodiments, the gas includes carbon dioxide. In some embodiments, the gas includes ammonia. In other embodiments, the gas includes hydrogen sulfide. In some embodiments, the gas includes methane. In some embodiments, the gas includes hydrogen. In other embodiments, the gas includes nitrogen. In some embodiments, the gas includes argon. Also, in some embodiments, the gas includes helium.

[0147] In some embodiments, the gas is introduced into the heating chamber at a flow rate of approximately 1 SCCM to approximately 3,000 SCCM. For example, the gas is introduced into the heating chamber at a flow rate of approximately 1,000 SCCM to approximately 3,000 SCCM. In other embodiments, the gas is introduced into the heating chamber at a flow rate of approximately 1,500 SCCM to approximately 2,500 SCCM. In some embodiments, the gas is introduced into the heating chamber at a flow rate of approximately 1 SCCM to approximately 1,500 SCCM. Also, in some embodiments, the gas is introduced into the heating chamber at a flow rate of approximately 1,500 SCCM to approximately 3,000 SCCM.

[0148] In some embodiments, step (d) is carried out at least partially during step (c). In other embodiments, the atmosphere inside the heating chamber during step (c) includes carbon monoxide, carbon dioxide, ammonia, hydrogen sulfide, methane, hydrogen, nitrogen, argon, helium, or any combination thereof.

[0149] In some embodiments, the method is (e) Further including repeating step (c).

[0150] In some embodiments, the lithium source is further defined as a first lithium source, and step (e) is: (e-1) After step (c), replace the first lithium source in the heating chamber with the second lithium source, and (e-2) This includes repeating step (c).

[0151] In some embodiments, the method further includes cooling the heating chamber before step (e-1). For example, the method may include cooling the heating chamber to room temperature before step (e-1). In other embodiments, the method may include cooling the heating chamber to below about 100°C before step (e-1). Also, in some embodiments, the method may include cooling the heating chamber to below about 50°C before step (e-1).

[0152] In some embodiments, the method is (f) The procedure further includes cleaning the substrate before step (a).

[0153] It should be understood that the substrate can be cleaned in any suitable way sufficient to prepare the surface of the substrate for coating. For example, step (f) may include cleaning the substrate using a sonicator (e.g., an ultrasonic device) before step (a). The substrate may be placed in a solvent (e.g., isopropanol) for cleaning with the sonicator.

[0154] In some embodiments, the method is (g) Further includes washing the setter body after step (c).

[0155] It should be understood that the setter body can be cleaned by any suitable method. For example, step (g) may include cleaning the setter body after step (c) using a sonicator (e.g., an ultrasonic device). The setter body may be placed in a solvent (e.g., water) for cleaning with the sonicator.

[0156] In another aspect, the present invention provides a method for forming a setter body for sintering a solid electrolyte material. The method is: (Ia) Placing a substrate in a heating chamber, wherein the substrate has a first surface, a second surface opposite to the first surface, and an outer surface extending from the first surface to the second surface, and the substrate contains nickel. (Ib) A lithium source is provided in the heating chamber, and (Ic) Heating the heating chamber to a temperature of approximately 800°C to approximately 1,200°C to form a coating on the first surface of the substrate that contains lithium from a lithium source at least partially, thereby forming a setter body. The coating contains at least about 1 mole percent of lithium (e.g., at least about 5 mole percent, or about 5 mole percent to about 50 mole percent).

[0157] In a further embodiment, the present invention provides a method for forming a setter body for sintering a solid electrolyte material. The method is: (II-a) Placing a substrate in a heating chamber, wherein the substrate has a first surface, a second surface opposite to the first surface, and an outer surface extending from the first surface to the second surface, and the substrate contains nickel. (II-b) Bringing a lithium source into the heating chamber, wherein the lithium source includes LLZO, and (II-c) Heating the heating chamber to a temperature of approximately 600°C to approximately 1,500°C to form a coating on the first surface of the substrate that contains at least partially lithium from a lithium source, thereby forming a setter body. The coating contains at least about 1 mole percent of lithium (e.g., at least about 5 mole percent, or about 5 mole percent to about 50 mole percent).

[0158] In yet another aspect, the present invention provides a method for forming a setter body for sintering a solid electrolyte material. The method is: (III-a) Placing a substrate in a heating chamber, wherein the substrate has a first surface, a second surface opposite to the first surface, and an outer surface extending from the first surface to the second surface, and the substrate contains nickel. (III-b) A lithium source is provided in the heating chamber, and (III-c) Heating the heating chamber to a temperature of approximately 600°C to approximately 1,500°C to form a coating on the first surface of the substrate that contains at least partially lithium from a lithium source, thereby forming a setter body, wherein the coating contains at least approximately 1 mole percent of lithium (e.g., at least approximately 5 mole percent, or approximately 5 mole percent to approximately 50 mole percent), and (III-d) During step (c), a gas is flowed into the heating chamber, at least partially, the gas comprising carbon monoxide, carbon dioxide, ammonia, hydrogen sulfide, methane, hydrogen, nitrogen, argon, helium, or any combination thereof.

[0159] In another aspect, the present invention provides a method for forming a setter body for sintering a solid electrolyte material. The method is: (IV-a) Placing a substrate in a heating chamber, wherein the substrate has a first surface, a second surface opposite to the first surface, and an outer surface extending from the first surface to the second surface, and the substrate contains nickel. (IV) A lithium source shall be provided in the heating chamber. (IV-c) Heating the heating chamber to a temperature of approximately 600°C to approximately 1,500°C to form a coating on the first surface of the substrate that contains at least partially lithium from a lithium source, thereby forming a setter body, wherein the coating contains at least approximately 1 mole percent lithium. (IV-d) During step (c), a gas is flowed into the heating chamber, at least partially, the gas comprising carbon monoxide, carbon dioxide, ammonia, hydrogen sulfide, methane, hydrogen, nitrogen, argon, helium, or any combination thereof, and (IV-f) The procedure includes cleaning the substrate before step (a).

[0160] In one embodiment, the present invention provides a method for forming a setter body for sintering a solid electrolyte material. The method is as follows: (Va) Placing a substrate in a heating chamber, wherein the substrate has a first surface, a second surface opposite the first surface, and an outer surface extending from the first surface to the second surface, and the substrate contains nickel. (Vb) Bringing a lithium source into the heating chamber, wherein the lithium source includes LLZO, (Vc) Heating the heating chamber to a temperature of approximately 600°C to approximately 1,500°C to form a coating on the first surface of the substrate that contains at least partially lithium from a lithium source, thereby forming a setter body, wherein the coating contains at least approximately 1 mole percent of lithium (e.g., at least approximately 5 mole percent, or approximately 5 mole percent to approximately 50 mole percent). (Vd) During step (c), a gas is flowed into the heating chamber, at least partially, the gas comprising carbon monoxide, carbon dioxide, ammonia, hydrogen sulfide, methane, hydrogen, nitrogen, argon, helium, or any combination thereof, and (Vf) The procedure includes cleaning the substrate before step (a).

[0161] IV. Method for forming sintered solid electrolyte materials

[0162] Another aspect of the present invention provides a method for forming a sintered solid electrolyte material. Referring to Figure 6, a flowchart illustrating an exemplary embodiment for forming a sintered solid electrolyte material is presented. The method is as follows: (aa) Placing a setter body in the heating chamber, the setter body is A substrate having a first surface, a second surface opposite the first surface, and an outer surface extending from the first surface to the second surface, wherein the substrate contains nickel, and A coating disposed at least partially on a first surface of a substrate, wherein the coating contains at least about 1 mole percent (e.g., at least about 5 mole percent or about 5 mole percent to about 50 mole percent) of lithium, and the mole percent of lithium in the coating is greater than the mole percent of lithium in the substrate (6002), (bb) Placing a green body on a setter body coating, wherein the green body includes a solid electrolyte material, (6004), and (cc) Heating the heating chamber to a temperature of approximately 600°C to approximately 1,500°C to form a sintered solid electrolyte (6006), The solid electrolyte material loses less than approximately 20 mole percent of lithium in a step (cc).

[0163] The setter body may be any setter body described herein. In some embodiments, step (aa) includes placing a plurality of setter bodies in the heating chamber. In some embodiments, a plurality of substrates may be placed in the heating chamber as a stack of setter bodies.

[0164] In some embodiments, the green body is a tape or film. The green body may include any suitable solid electrolyte material for use in a solid battery cell. For example, in some embodiments, the solid electrolyte material may include a garnet material. Non-limiting examples of garnet materials include lithium garnet materials, doped lithium garnet materials, lithium garnet composite materials, and combinations thereof. Non-limiting examples of lithium garnet materials include Li3-phase lithium garnet solid electrolyte materials (e.g., Li3M 1 Te2O 12 , here, M 1 These include lanthanides such as Y, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Zr, Ta, or combinations thereof, and Li 3+x Nd3Te 2-x O 12 Here, x is 0.05 to 1.5, and the Li5-phase lithium garnet solid electrolyte material is (e.g., Li5La3M) 2 20 12 Here M 2 This includes Nb, Zr, Ta, Sb, or combinations thereof, and cation-substituted Li5La3M. 2 20 12 For example, Li6M 1 La3 M 2 20 12 Here M 1 These are Mg, Ca, Sr, Ba, or combinations thereof, and Li7La3M 2 20 12 Here M 2 (e.g., Zr, Sn, or a combination thereof), Li6-phase lithium garnet solid electrolyte material (e.g., Li6M 1 La2 M 2 20 12 Here M 1 M is Mg, Ca, Sr, Ba, or a combination thereof. 2 (is Nb, Ta, or a combination thereof), cation-doped Li6La2BaTa2O 12 , cation-doped Li6BaY2M 2 20 12 Here M 2is Nb, Ta, or a combination thereof, and the cation dopant is barium, yttrium, zinc, or a combination thereof, a Li7 phase lithium garnet solid electrolyte material (for example, cubic Li7La3Zr2O 12 and Li7Y3Zr2O 12 ), cation-doped Li7La3Zr2O 12 , Li 5+2x La3, Ta 2-x O2, where x is 0.1 to 1, Li 6.8 (La 2.95 , Ca 0.5 )(Zr 1.75 , Nb 0.25 )O 12 (LLCZN), Li 6.4 Y3Zr 1.4 Ta 0.6 O 12 , Li 6.5 La 2.5 Ba 0.5 TaZrO 12 , Li6BaY2M 1 2O 12 , Li7Y3Zr2O 12 , Li 6.75 BaLa2Nb 1.75 Zn 0.25 O 12 , or Li 6.75 BaLa2Ta 1.75 Zn 0.25 O 12 ), and lithium garnet composite materials (for example, a composite material of lithium garnet and a conductive carbon matrix or other materials). Other examples of lithium ion conductive solid electrolyte materials include 3 mol% YSZ doped Li 7.6 La3Zr 1.94 Y 0.06 O 12 and 8 mol% YSZ doped Li 7.16 La3Zr 1.94 Y 0.06 O 12 and other cubic garnet type materials. Further examples of suitable lithium garnet solid electrolyte materials include Li5La3Nb2O 12 , Li5La3Ta2O 12 , Li7La3Zr2O 12, Li6La2SrNb2O 12 , Li6La2BaNb2O 12 , Li6La2SrTa2O 12 , Li6La2BaTa2O 12 , Li7Y3Zr2O 12 , Li 6.4 Y3Zr 1.4 Ta 0.6 O 12 , Li 6.5 La 2.5 Ba 0.5 TaZrO 12 , Li7Y3Zr2O 12 , Li 6.75 BaLa2Nb 1.75 Zn 0.25 O 12 , or Li 6.75 BaLa2Ta 1.75 Zn 0.25 O 12 is included, but not limited thereto. In some embodiments, the garnet material is, for example, Li 7-x La 3-y M 1 y Zr 2-Z M 2 Z O 12 , where x is greater than 0 and less than 2, M 1 is selected from Ba, Ca, Y, and combinations thereof, and M 2 is selected from Nb, Ta, and combinations thereof. In some embodiments, the garnet material is Li 6.75 La3Zr 1.75 Ta 0.25 O 12 (LLZT), Li 6.75 La 2.75 Zr 1.75 Ca 0.25 Nb 0.25 O 12 (LLZCN), Li5La3Nb2O 12 (LLZNO), Li7La3Zr2O 12 (LLZ), Li5La3Ta2O 12 , Li6La2SrNb2O 12 , Li6La2BaNb2O 12Li6La2SrTa2O 12 Li6La2BaTa2O 12 Li7Y3Zr2O 12 Li 6.4 Y3Zr 1.4 Ta 0.6 O 12 Li 6.5 La 2.5 Ba 0.5 GaZrO 12 Li6BaY2M 1 20 12 Li 6.75 BaLa2Nb 1.75 Zn 0.25 O 12 Li 6.75 BaLa2Ta 1.75 Zn 0.25 O 12 , or any combination thereof.

[0165] In some embodiments, the garnet material comprises a composition of formula (I). M1 7-x D1 a M2 3-y D2 b M3 2-z D3 c O 12-w D4 d (I) During the ceremony, M1 is Li, M2 is La, M3 is Zr, D1 is H, Be, B, Al, Fe, Zn, Ga, Ge, or any combination thereof. D2 is Na, K, Ca, Rb, Sr, Y, Ag, Ba, Bi, Pr, Nd, Pm, Sm, Gd, Tb, Dy, Ho, Er, Tm, Zn, Ce, or any combination thereof. D3 is Mg, Si, Sc, Ti, V, Cr, Mn, Co, Ni, Cu, Ge, As, Se, Nb, Mo, Tc, Ru, Rh, Pd, Cd, In, Sn, Sb, Hf, Ta, W, Ir, Pt, Au, Hg, Tl, Pb, Ce, Eu, Te, Y, Sr, Ca, Ba, Gd, Ge, or any combination thereof. D4 is F, Cl, Br, I, S, Se, Te, N, P, or any combination thereof. 0 ≤ w ≤ 2, -0.5 <x≦3、 0≦y≦3, 0≦z≦2, 0 ≤ a ≤ 2, 0 ≤ b ≤ 3, 0 ≤ c ≤ 2, and, 0 ≤ d ≤ 2, At least one of a, b, c, and d is not 0.

[0166] In some embodiments, the green body comprises at least one of a pore-forming agent and a binder. In some embodiments, the green body comprises a pore-forming agent. In other embodiments, the green body comprises a binder. Also in some embodiments, the green body comprises a binder and a pore-forming agent. The binder and pore-forming agent may be any binder and pore-forming agent suitable for use in the solid electrolyte material of a battery cell.

[0167] In some embodiments, the solid electrolyte material loses less than approximately 15 mole percent of lithium during the step (cc). In other embodiments, the solid electrolyte material loses less than approximately 10 mole percent of lithium during the step (cc). Also, in some embodiments, the solid electrolyte material loses less than approximately 7.5 mole percent of lithium during the step (cc).

[0168] In some embodiments, step (cc) includes heating the heating chamber to a temperature of about 700°C to about 1,500°C (e.g., about 700°C to about 1,200°C). In other embodiments, step (cc) includes heating the heating chamber to a temperature of about 800°C to about 1,500°C (e.g., about 800°C to about 1,200°C). In some embodiments, step (cc) includes heating the heating chamber to a temperature of about 900°C to about 1,500°C (e.g., about 900°C to about 1,200°C). In some embodiments, step (cc) also includes heating the heating chamber to a temperature of about 1,000°C to about 1,500°C (e.g., about 1,000°C to about 1,200°C).

[0169] In some embodiments, the method is (dd) Further includes introducing gas into the heating chamber.

[0170] In some embodiments, the gas includes carbon monoxide, carbon dioxide, ammonia, hydrogen sulfide, methane, hydrogen, nitrogen, argon, helium, or any combination thereof. In other embodiments, the gas includes a mixture of hydrogen and an inert gas (e.g., nitrogen). For example, the gas may include carbon monoxide. In some embodiments, the gas includes carbon dioxide. In some embodiments, the gas includes ammonia. In other embodiments, the gas includes hydrogen sulfide. In some embodiments, the gas includes methane. In some embodiments, the gas includes hydrogen. In other embodiments, the gas includes nitrogen. In some embodiments, the gas includes argon. Also, in some embodiments, the gas includes helium.

[0171] In some embodiments, the gas is introduced into the heating chamber at a flow rate of approximately 1 SCCM to approximately 3,000 SCCM. For example, the gas is introduced into the heating chamber at a flow rate of approximately 1,000 SCCM to approximately 3,000 SCCM. In other embodiments, the gas is introduced into the heating chamber at a flow rate of approximately 1,500 SCCM to approximately 2,500 SCCM. In some embodiments, the gas is introduced into the heating chamber at a flow rate of approximately 1 SCCM to approximately 1,500 SCCM. Also, in some embodiments, the gas is introduced into the heating chamber at a flow rate of approximately 1,500 SCCM to approximately 3,000 SCCM.

[0172] In some embodiments, step (dd) is carried out at least partially during step (cc). In other embodiments, the atmosphere inside the heating chamber during step (cc) includes carbon monoxide, carbon dioxide, ammonia, hydrogen sulfide, methane, hydrogen, nitrogen, argon, helium, or any combination thereof.

[0173] In some embodiments, the atmospheric pressure inside the heating chamber between steps (cc) is about 1 Pa to about 10 MPa. In other embodiments, the atmospheric pressure inside the heating chamber between steps (cc) is about 1 MPa to about 10 MPa. In some embodiments, the atmospheric pressure inside the heating chamber between steps (cc) is about 1 Pa to about 1 MPa. In some embodiments, the atmospheric pressure inside the heating chamber between steps (cc) is about 1 MPa to about 2 MPa. In some embodiments, the atmospheric pressure inside the heating chamber between steps (cc) is about 2 MPa to about 3 MPa. In other embodiments, the atmospheric pressure inside the heating chamber between steps (cc) is about 3 MPa to about 4 MPa. In some embodiments, the atmospheric pressure inside the heating chamber between steps (cc) is about 4 MPa to about 5 MPa. In some embodiments, the atmospheric pressure inside the heating chamber between steps (cc) is about 5 MPa to about 6 MPa. In other embodiments, the atmospheric pressure inside the heating chamber between steps (cc) is about 6 MPa to about 7 MPa. In some embodiments, the atmospheric pressure inside the heating chamber between steps (cc) is approximately 7 MPa to approximately 8 MPa. In some embodiments, the atmospheric pressure inside the heating chamber between steps (cc) is approximately 8 MPa to approximately 9 MPa. In some embodiments, the atmospheric pressure inside the heating chamber between steps (cc) is approximately 9 MPa to approximately 10 MPa.

[0174] In some embodiments, if the green body further comprises at least one of a binder and a pore-forming agent, step (cc) is: (cc-1) Heat the heating chamber to a first temperature of approximately 400°C to approximately 800°C to burn at least one of the pore-forming agent and the binder, and (cc-2) Heating the heating chamber to a second temperature of approximately 600°C to approximately 1,500°C (for example, approximately 600°C to approximately 1,200°C) to form a sintered solid electrolyte, further comprising heating such that the second temperature is higher than the first temperature.

[0175] In some embodiments, step (cc-1) includes heating the heating chamber to a temperature of about 450°C to about 750°C. In other embodiments, step (cc-1) includes heating the heating chamber to a temperature of about 500°C to about 700°C. Also in some embodiments, step (cc-1) includes heating the heating chamber to a temperature of about 600°C to about 700°C.

[0176] In some embodiments, step (cc-2) includes heating the heating chamber to a temperature of about 700°C to about 1,500°C (e.g., about 700°C to about 1,200°C). In other embodiments, step (cc-2) includes heating the heating chamber to a temperature of about 800°C to about 1,500°C (e.g., about 800°C to about 1,200°C). In some embodiments, step (cc-2) includes heating the heating chamber to a temperature of about 900°C to about 1,500°C (e.g., about 900°C to about 1,200°C). In some embodiments, step (cc-2) also includes heating the heating chamber to a temperature of about 1,000°C to about 1,200°C (e.g., about 1,000°C to about 1,200°C).

[0177] In some embodiments, if step (cc) includes steps (cc-1) and (cc-2), the method (dd-1) During step (cc-1), at least partially, the first gas is introduced into the heating chamber, and (dd-2) This may further include introducing at least partially the second gas into the heating chamber during step (cc-2).

[0178] In some embodiments, the first gas in step (dd-1) is selected from oxygen, dry air, or air.

[0179] In some embodiments, the second gas in step (dd-2) is selected from carbon monoxide, carbon dioxide, ammonia, hydrogen sulfide, methane, hydrogen, nitrogen, argon, helium, or any combination thereof. In other embodiments, the second gas includes a mixture of hydrogen and an inert gas (e.g., nitrogen). In some embodiments, the second gas includes carbon monoxide. In some embodiments, the second gas includes carbon dioxide. In some embodiments, the second gas includes ammonia. In other embodiments, the second gas includes hydrogen sulfide. In some embodiments, the second gas includes methane. In some embodiments, the second gas includes hydrogen. In other embodiments, the second gas includes nitrogen. In some embodiments, the second gas includes argon. Also, in some embodiments, the second gas includes helium.

[0180] In some embodiments, the first gas is introduced into the heating chamber at a flow rate of approximately 1 SCCM to approximately 3,000 SCCM. For example, the first gas is introduced into the heating chamber at a flow rate of approximately 1,000 SCCM to approximately 3,000 SCCM. In other embodiments, the first gas is introduced into the heating chamber at a flow rate of approximately 1,500 SCCM to approximately 2,500 SCCM. In some embodiments, the first gas is introduced into the heating chamber at a flow rate of approximately 1 SCCM to approximately 1,500 SCCM. Also, in some embodiments, the first gas is introduced into the heating chamber at a flow rate of approximately 1,500 SCCM to approximately 3,000 SCCM.

[0181] In some embodiments, the second gas includes carbon monoxide, carbon dioxide, ammonia, hydrogen sulfide, methane, hydrogen, nitrogen, argon, helium, or any combination thereof. In other embodiments, the second gas includes a mixture of hydrogen and an inert gas (e.g., nitrogen). For example, the second gas may include carbon monoxide. In some embodiments, the second gas includes carbon dioxide. In some embodiments, the second gas includes ammonia. In other embodiments, the second gas includes hydrogen sulfide. In some embodiments, the second gas includes methane. In some embodiments, the second gas includes hydrogen. In other embodiments, the second gas includes nitrogen. In some embodiments, the second gas includes argon. Also, in some embodiments, the second gas includes helium.

[0182] In some embodiments, the second gas is introduced into the heating chamber at a flow rate of approximately 1 SCCM to approximately 3,000 SCCM. For example, the second gas is introduced into the heating chamber at a flow rate of approximately 1,000 SCCM to approximately 3,000 SCCM. In other embodiments, the second gas is introduced into the heating chamber at a flow rate of approximately 1,500 SCCM to approximately 2,500 SCCM. In some embodiments, the second gas is introduced into the heating chamber at a flow rate of approximately 1 SCCM to approximately 1,500 SCCM. Also, in some embodiments, the second gas is introduced into the heating chamber at a flow rate of approximately 1,500 SCCM to approximately 3,000 SCCM.

[0183] In some embodiments, the method is (ee) Further comprising cooling the heating chamber after step (cc).

[0184] For example, the method may include cooling the heating chamber to room temperature after step (cc). In other embodiments, the method may include cooling the heating chamber to below about 100°C after step (cc). Also, in some embodiments, the method may include cooling the heating chamber to below about 50°C after step (cc).

[0185] In another aspect, the present invention provides a method for forming a sintered solid electrolyte material. The method is: (I-aa) Placing a setter body in the heating chamber, the setter body is A substrate having a first surface, a second surface opposite the first surface, and an outer surface extending from the first surface to the second surface, wherein the substrate contains nickel, and A coating, at least partially disposed on a first surface of a substrate, wherein the coating contains at least about 1 weight percent of lithium based on the total weight of the coating, and the weight percent of lithium in the coating is greater than the weight percent of lithium in the substrate, is disposed of. (I-bb) Placing a green body on a setter body coating, wherein the green body includes a solid electrolyte material, and (I-cc) The heating chamber is heated to a temperature of approximately 600°C to approximately 1,200°C to form a sintered solid electrolyte. The solid electrolyte material loses less than approximately 20 mole percent of lithium in step (1-cc).

[0186] In a further embodiment, the present invention provides a method for forming a sintered solid electrolyte material. The method is: (II-aa) Placing a setter body in the heating chamber, the setter body is A substrate having a first surface, a second surface opposite the first surface, and an outer surface extending from the first surface to the second surface, wherein the substrate contains nickel, and A coating is provided, at least partially, on a first surface of a substrate, wherein the coating contains at least about 1 mole percent of lithium, and the mole percent of lithium in the coating is greater than the mole percent of lithium in the substrate. (II-bb) Placing a green body on a setter body coating, wherein the green body comprises a solid electrolyte material and at least one of a pore-forming agent and a binder. (II-cc-1) Heat the heating chamber to a first temperature of approximately 400°C to approximately 800°C to burn at least one of the pore-forming agent and the binder, and (II-cc-2) Heating the heating chamber to a second temperature of approximately 600°C to approximately 1,500°C to form a sintered solid electrolyte, wherein the second temperature is higher than the first temperature, The solid electrolyte material loses less than approximately 20 mole percent of lithium in steps (II-cc-1) and (II-cc-2).

[0187] In yet another aspect, the present invention provides a method for forming a sintered solid electrolyte material. The method is: (III-aa) Placing a setter body in the heating chamber, the setter body is A substrate having a first surface, a second surface opposite the first surface, and an outer surface extending from the first surface to the second surface, wherein the substrate contains nickel, and A coating is provided, at least partially, on a first surface of a substrate, wherein the coating contains at least about 1 mole percent of lithium, and the mole percent of lithium in the coating is greater than the mole percent of lithium in the substrate. (III-bb) Placing a green body on a setter body coating, wherein the green body comprises a solid electrolyte material and at least one of a pore-forming agent and a binder. (III-cc-1) Heat the heating chamber to a first temperature of approximately 400°C to approximately 800°C to burn at least one of the pore-forming agent and the binder. (III-cc-2) Heating the heating chamber to a second temperature of approximately 600°C to approximately 1,500°C to form a sintered solid electrolyte, wherein the second temperature is higher than the first temperature. (III-dd-1) During step (cc-1), at least partially the first gas is introduced into the heating chamber, and (III-dd-2) Step (cc-2) includes at least partially introducing the second gas into the heating chamber, The solid electrolyte material loses less than about 20 mole percent of lithium in step (III-cc-1) and step (III-cc-2).

[0188] [Examples]

[0189] In order to more fully understand the invention described in the present specification, the following examples are described. The examples described in the present application are provided to illustrate the methods and setter bodies provided herein, and shall not be construed as limiting their scope in any respect.

[0190] Example 1: Setter body for sintering solid electrolyte material

[0191] Two nickel mesh substrates manufactured by Belleville Wire Cloth Company, size 100×100, area 8cm×11cm, and areal density 0.13g / cm 2 (Grade 200, Ni purity 99% or more, Si less than 0.35%, Fe less than 0.40%, Ti less than 0.01%, Co less than 0.01%, Mg less than 0.004%) (i.e., the first substrate and the second substrate) were cleaned in isopropanol for 5 minutes by ultrasonic cleaning. Figures 7A and 7B present images of representative portions of the first and second nickel mesh substrates before cleaning (Figure 7A) and after cleaning (Figure 7B). The image in Figure 7A was obtained at a magnification of 1600× using the following microscope settings / parameters and a background scatter detector. · FW (Field Width) = 374μm · HV = 15kV, · Int. = Map · WD (Working Distance) 4.833mm, and · Pressure = 0.10Pa. The image in Figure 7B was obtained at a magnification of 1000× using the following microscope settings / parameters and a background scatter detector. · FW (Field Width) = 519μm · HV = 15kV, Int. = Map • WD (working distance) 6.072 mm, and Pressure = 0.10 Pa.

[0192] Referring to Figure 8, the first substrate 802a was placed on the first nickel plate 812a having a thickness of 1.56 mm (McMaster 200 grade, Ni purity 99% or higher), and an undoped LLZO (18 g) powder bed 814 was uniformly applied to the first substrate on top of the first nickel plate 812a. The second substrate 802b was placed on top of the powder bed. The second nickel plate 812b was placed on top of the second substrate 802b. The resulting stack was heated at 1,100°C for 2 hours (lamp injection from room temperature at 3°C / min in forming gas, pO2 < 10°C -23 The flow rate was set to 2,000 SCCM at atm. The forming gas used was 0.4% H2 in Ar.

[0193] Setter body - Nickel mesh substrate

[0194] The resulting first and second setter bodies, formed from the cleaned nickel mesh substrates, were removed from the stack and ultrasonically cleaned in water for 5 minutes before use. Figure 9 shows partial images of the nickel mesh setter bodies formed from the substrates of Figures 7A and 7B. The images in Figure 9 were obtained at 1600x magnification using the following microscope settings / parameters and background scattering detector. • FW (Field width) = 374 μm HV = 15kV, Int. = Map • WD (working distance) 4,860 mm, and Pressure = 0.10 Pa. The nickel mesh setter body contains multiple nodules extending away from the substrate surface. SEM-EDX determined that the nodules contain aluminum, silicon, magnesium, calcium, and / or oxygen.

[0195] Setter body - Nickel plated substrate

[0196] One of the nickel plate setter bodies obtained by forming nickel plates 812a and 812b underwent XPS analysis.

[0197] XPS analysis method

[0198] The nickel-plated setter body underwent an investigation scan, followed by depth profile / high-resolution scans of the detected species at depths of 0 nm, 50 nm, 100 nm, and 150 nm with respect to the SiO2 sputtering rate, using the following parameters.

[0199] Parameters to be retrieved: • Dual-beam charge neutralization consisting of electrons and low-energy argon ions for all scans. • Monochromatic Al K α It is operated using a 50W, 200μm X-ray beam (1486.6eV) that rasterizes a single point at the center of the sputter crater during depth profiling. • Investigation scan: 45° photoelectron extraction angle, 280eV analyzer pass energy, 1.0eV / step. • High-resolution scanning: 45° photoelectron extraction angle, variable analyzer path energy to maximize the analysis signal, and eV step size, • The energy scale of the high-resolution spectrum refers to the position of the C1s peak of the carbonate bond at 290.1 ​​eV.

[0200] Depth profile sputtering parameters: • 4keV Ar + Beam energy, beam current of 1 μA, raster area of ​​3 mm × 3 mm, total duration of 50 minutes at 16.7 minute intervals, and • Sputtering rate of 100nm SiO2 reference sample: 3.6nm / min.

[0201] Referring to Figure 10, XPS analysis detected no nickel right at the surface of the setter body, and the scanned surface was almost entirely (or entirely) coated with oxidized lithium. The oxygen signal from the XPS scan indicates that the coating contains Li2CO3, with trace amounts of Li2O on the surface. The carbon signal also supports this finding.

[0202] The surface of the setter body was sputtered at predetermined intervals at an estimated depth of about 160 nm. At this first depth, nickel metal was detected, and no oxidized forms of nickel were detected. As the depth increases, the concentration of nickel increases, but the total concentration of lithium remains relatively consistent with depth, which indicates some penetration of oxidized lithium into the nickel substrate. LiOH, Li2O, and Li2CO3 were all detected below the surface.

[0203] Example 2: Sintering of Solid Electrolyte Materials

[0204] Referring to Figure 11, a setter body coated and formed according to Example 1 is shown, in which a nickel plate substrate 1012 is placed in a furnace and a green two-layer tape 1016 (8 cm × 11 cm) is placed on the setter body. The green two-layer tape was composed of doped LLZO. The tape further contained a porous layer 1018 (thickness 40 μm) containing a pore-forming agent and a dense layer 1020 containing excess lithium (i.e., 15% lithium exceeding the stoichiometric amount from Li2CO3). The porous layer was placed in contact with the setter body 1012. One of the setter bodies having a nickel mesh substrate 1000 obtained from Example 1 was placed on top of the two-layer tape in contact with the dense layer. The resulting stack was heated in UHPO2 from room temperature to 580°C at 0.4°C / min and held at 2,000 SCCM for 30 minutes to burn off the binder and pore-forming agent. While maintaining that temperature, argon was flowed through the furnace at 2,000 SCCM for 30 minutes. Subsequently, the temperature was maintained while the forming gas was flowed into the furnace at 2,000 SCCM for 30 minutes. The furnace temperature was increased from 580°C to 725°C at a rate of 1°C / min and then held for 1 hour. Next, the furnace temperature was increased to 1,100°C at a rate of 3°C / min for 2 hours. Finally, the furnace was cooled at a rate of 3°C / min. Throughout all steps after the debonding step, pO2 was 10 -23 The pressure was less than atm. The resulting product was a sintered two-layer solid electrolyte material containing a porous layer and a dense layer.

[0205] Referring to Figures 12A-12D, setter bodies 1012 and 1000 were recovered and reused in 10 additional sintering processes consistent with those described above to produce a sintered two-layer solid electrolyte material, demonstrating that the setter bodies are resistant to (and recyclable from) the high-temperature sintering process of the LLZO solid electrolyte material. The microscopic image in Figure 12B was obtained at 2500x magnification using the following microscope settings / parameters and background scattering detector. • FW (Field Width) = 239 μm HV = 15kV, Int. = Image • WD (working distance) 6,560 mm, and Pressure = 0.10 Pa.

[0206] The microscope image in Figure 12C was obtained at a magnification of 2500x using the following microscope settings / parameters and background scattering detector. • FW (Field Width) = 239 μm HV = 15kV, Int. = Image • WD (working distance) 7.057 mm, and Pressure = 0.10 Pa.

[0207] The microscope image in Figure 12D was obtained at a magnification of 2500x using the following microscope settings / parameters and background scattering detector. • FW (Field Width) = 239 μm HV = 15kV, Int. = Image • WD (working distance) 6.922 mm, and Pressure = 0.10 Pa.

[0208] As shown in Figures 12A to 12D, these coated nickel setter bodies can be used (and / or reused) in at least 11 sintering processes, and an LLZO solid electrolyte material can be produced without the need to add excess lithium in the sintering process and without significant lithium depletion in the resulting sintered material.

[0209] Example 3: Setter body for sintering solid electrolyte material

[0210] A setter substrate was tested using ferrous metal (99.5% purity). An undoped LLZO powder bed (12 g) was spread uniformly over an iron plate measuring 3.25 inches × 5.5 inches × 0.005 inches. The resulting stack was heated at 1,100°C for 2 hours (lamp injection from room temperature at 3°C / min in forming gas, pO2 < 10°C). -23At an atm (atm), the flow rate was increased to 2,000 SCCM to generate a coating and form a setter body. The cooled powder bed substantially adhered to the iron plate, and the iron plate discolored to brown and black. The discoloration of the plate indicates oxidation of the plate surface, and the adhesion of the powder to the plate indicates a reaction between the powder and the iron plate.

[0211] A setter body having an iron plate substrate was placed in the furnace, and a two-layer green tape (6 cm × 9 cm) was placed on the setter body as shown in Figure 11 and as described in Example 1. The two-layer green tape was composed of doped LLZO. The tape further contained a porous layer (40 μm thick) containing a pore-forming agent and a dense layer containing doped LLZO. The porous layer was placed in contact with the setter body. A setter body having a nickel mesh substrate, produced according to the process described in Example 1, was placed on top of the two-layer tape in contact with the dense layer. The resulting stack was heated in dry air from room temperature to 640 °C at 0.4 °C / min and held at 2,000 SCCM for 30 minutes to burn off the binder and pore-forming agent. While maintaining the temperature, argon was flowed through the furnace at 2,000 SCCM for 30 minutes. Afterwards, the temperature was maintained while forming gas was flowed into the furnace at 2,000 SCCM for 30 minutes. Next, the furnace temperature was increased to 1,100°C at a rate of 3°C / min for 2 hours. Finally, the furnace was cooled at a rate of 5°C / min. Throughout all steps after the binder removal step, the pO2 was 10 -23 The pressure was less than atm. The resulting product was a two-layer solid electrolyte material with insufficient sintering, containing a porous layer and a dense layer. Referring to Figure 13A, the dense layer was not uniformly dense and was substantially porous. Furthermore, as shown in Figure 13B, iron was detected in the dense layer by SEM-EDX analysis. This Example 3 demonstrates that iron in the setter body interacted with the LLZO solid electrolyte material. Therefore, iron was not a suitable setter substrate for sintering the LLZO material.

[0212] The microscope image in Figure 13A was obtained at a magnification of 2500x using the following microscope settings / parameters and background scattering detector. • FW (Field Width) = 239 μm HV = 15kV, Int. = Image • WD (working distance) 6.589 mm, and Pressure = 0.10 Pa.

[0213] Example 4: Invar alloy setter body for sintering solid electrolyte material

[0214] An Invar alloy, composed of 64 wt% iron and 36 wt% nickel, was used as the setter substrate for testing. An undoped LLZO powder bed (12 g) was spread uniformly across a 3.25 inch × 5.5 inch × 0.005 inch Invar alloy plate. The resulting stack was heated at 1,100°C for 2 hours (lamp injection from room temperature at 3°C / min in forming gas, pO2 < 10°C). -23 At an atm (atm), the flow rate was increased to 2,000 SC / cm² to generate a coating and form a coated setter body. Some of the powder bed adhered to the Monel 400 plate but was easily removed. The plate retained a substantially metallic color.

[0215] A setter body having an Invar alloy plate substrate was placed in the furnace, and a two-layer green tape (6 cm × 9 cm) was placed on the setter body as shown in Figure 11 and as described in Example 1. The two-layer green tape was composed of doped LLZO. The tape further contained a porous layer (40 μm thick) containing a pore-forming agent and a dense layer containing doped LLZO. The porous layer was placed in contact with the setter body. A setter body having a nickel mesh substrate, produced according to the process described in Example 1, was placed on top of the two-layer tape in contact with the dense layer. The resulting stack was heated in dry air from room temperature to 640 °C at 0.4 °C / min and held at 2,000 SCCM for 30 minutes to burn off the binder and pore-forming agent. While maintaining the temperature, argon was flowed through the furnace at 2,000 SCCM for 30 minutes. Subsequently, the temperature was maintained while forming gas was flowed into the furnace at 2,000 SCCM for 30 minutes. Next, the furnace temperature was increased to 1,100°C at a rate of 3°C / min for 2 hours. Finally, the furnace was cooled at a rate of 5°C / min. Throughout all steps after the binder removal step, the pO2 was 10 -23 The pressure was less than atm. The resulting product was a sintered LLZO two-layer solid electrolyte material containing a porous layer and a dense layer. The dense layer was sufficiently dense. The sintered two layers were discolored light brown in some areas. However, iron was detected in the dense layer by SEM-EDX analysis. Copper was not detected by SEM-EDX analysis. This example demonstrates that 64 weight percent of iron in the setter body interacted with the solid electrolyte material. Therefore, Invar was not a suitable setter substrate for sintering LLZO material.

[0216] Example 5: Monel alloy setter body for sintering solid electrolyte material

[0217] Monel 400 alloy (65 wt% nickel, 33 wt% copper, and 2 wt% iron) was used as the setter substrate for testing. An undoped LLZO powder bed (12 g) was spread uniformly over a 3.25 inch × 5.5 inch × 0.005 inch Monel 400 alloy plate (3.25 inch × 5.5 inch × 0.005 inch). The resulting stack was heated at 1,100°C for 2 hours (lamp injection from room temperature at 3°C / min in forming gas, pO2 < 10°C). -23 At an atm (atm), the flow rate was increased to 2,000 SCCM to generate a coating and form a setter body. Some of the powder bed adhered to the Monel 400 plate but was easily removed. The plate retained a substantially metallic color.

[0218] A setter body having a Monel 400 alloy plate substrate was placed in the furnace, and a two-layer green tape (6 cm × 9 cm) was placed on the setter body as shown in Figure 11 and as described in Example 1. The two-layer green tape was composed of doped LLZO. The tape further contained a porous layer (40 μm thick) containing a pore-forming agent and a dense layer containing doped LLZO. The porous layer was placed in contact with the setter body. One of the setter bodies having a nickel mesh substrate, produced according to the process described in Example 1, was placed on top of the two-layer tape in contact with the dense layer. The resulting stack was heated in dry air from room temperature to 640 °C at 0.4 °C / min and held at 2,000 SCCM for 30 minutes to burn off the binder and pore-forming agent. While maintaining that temperature, argon was flowed through the furnace at 2,000 SCCM for 30 minutes. Subsequently, the temperature was maintained while the forming gas was flowed into the furnace at 2,000 SCCM for 30 minutes. Then, the furnace temperature was increased to 1,100°C at a rate of 3°C / min for 2 hours. Finally, the furnace was cooled at a rate of 5°C / min. Throughout all steps after the binder removal step, the pO2 was 10 -23The pressure was less than atm. The resulting product was a sintered two-layer solid electrolyte material containing a porous layer and a dense layer. The dense layer was sufficiently dense. SEM-EDX analysis revealed no iron, copper, or nickel in the dense layer. The example demonstrates that 2 wt percent iron and 33 wt percent copper in the setter body did not substantially interact with the solid electrolyte material. Therefore, Monel 400 was a suitable setter substrate.

[0219] Example 6: Uncoated setter body for sintering solid electrolyte material

[0220] To demonstrate the importance of coating the setter body, solid electrolyte materials were sintered using uncoated nickel plates and uncoated nickel mesh. An untreated nickel plate was placed in a furnace, and a two-layer green body tape (6 cm × 9 cm) was placed on the plate. The two-layer green body tape consisted of doped LLZO. The tape further contained a porous layer (40 μm thick) containing a pore-forming agent and a dense layer containing doped LLZO. The porous layer was placed in contact with the plate. An untreated nickel mesh was placed on top of the two-layer tape in contact with the dense layer. The resulting stack was heated in dry air from room temperature to 640 °C at 0.4 °C / min and held at 2,000 SCCM for 30 minutes to burn off the binder and pore-forming agent. While maintaining the temperature, argon was flowed through the furnace at 2,000 SCCM for 30 minutes. Subsequently, the temperature was maintained while forming gas was flowed through the furnace at 2,000 SCCM for 30 minutes. Next, the furnace temperature was increased to 1,100°C at a rate of 3°C / min for 2 hours. Finally, the furnace was cooled at a rate of 5°C / min. Throughout all steps after the binder removal step, the pO2 was 10 -23 The pressure was less than atm. The resulting product was a poorly sintered two-layer solid electrolyte material containing a porous layer and a dense layer, as shown in Figure 14.

[0221] The microscope image in Figure 14 was obtained at a magnification of 2500x using the following microscope settings / parameters and background scattering detector. • FW (Field width) = 208 μm HV = 15kV, Int. = Image • WD (working distance) 4,900 mm, and Pressure = 0.10 Pa.

[0222] The resulting two-layer solid electrolyte, sintered using an uncoated Ni plate, was significantly deficient in lithium by 14%, as measured by ICP-OES. The resulting sintered two-layer solid electrolyte from Example 3, using a coated setter body, was measured for lithium content by ICP-OES and showed no measurable deficiency (0-1%). Equivalents and Scope

[0223] In the claims, articles such as “a,” “an,” and “the” may mean one or more unless otherwise indicated or the context makes it clear that they mean one or more. Claims or descriptions containing “or” between one or more components of a group are considered satisfied if one, two or more, or all of the components of the group are present, used, or related to a given product or process, unless otherwise indicated or the context makes it clear that they mean one or more. The present invention includes embodiments in which exactly one element of the group is present, used, or otherwise related to a given product or process. The present invention also includes embodiments in which two or more, or all, of the elements of the group are present, used, or otherwise related to a given product or process.

[0224] Furthermore, the present invention encompasses all variations, combinations, and substitutions in which one or more limitations, elements, clauses, and descriptive terms from one or more of the enumerated claims are introduced into another claim. For example, any claim dependent on another claim may be modified to include one or more limitations found in any other claim dependent on the same basic claim. Where elements are presented as a list, for example in Markush group form, each subgroup of elements is also disclosed, and any element(s) may be removed from this group. Naturally, generally, where the present invention or an aspect of the present invention is referred to as including certain elements and / or features, certain particular embodiments or aspects of the present invention consist of, or essentially consist of, such elements and / or features. For simplicity, these embodiments are not specifically described verbatim in this specification. Note that the terms “comprising” and “containing” are intended to be open and also allow for the inclusion of additional elements or steps. Where a scope is given, this includes endpoints. Furthermore, unless otherwise indicated, or unless it is clearly understood from the context and the understanding of those skilled in the art, any value expressed as a range may be considered any specific value or subrange within the defined range of different embodiments of the present invention, up to one-tenth of the lower limit unit of the range, unless it is clearly understood from the context.

[0225] This application references certain issued patents, published patent applications, journal articles, and other publications, all of which are incorporated herein by reference. In the event of any conflict between any of the referenced documents and this application, this specification shall prevail. Furthermore, any particular embodiment of the Invention within the scope of the prior art may be expressly excluded from any one or more of the claims. Such embodiments may be excluded even if not explicitly stated herein, as they are considered to be known to those skilled in the art. Any particular embodiment of the Invention may be excluded from any claim for any reason, whether or not relating to the existence of the prior art.

[0226] Those skilled in the art will be able to recognize or confirm many equivalents to the specific embodiments described herein using only routine experiments. The scope of the embodiments described herein is not intended to be limited to the above specification, but is as set out in the appended claims. Those skilled in the art will understand that various changes and modifications can be made to this specification without departing from the spirit or scope of the invention as defined in the following claims.

Claims

1. A setter body for sintering a solid electrolyte material, wherein the setter body is A substrate having a first surface, a second surface opposite to the first surface, and an outer surface extending from the first surface to the second surface, wherein the substrate contains nickel, and A setter body comprising a coating at least partially disposed on the first surface of the substrate, wherein the coating contains at least about 1 mole percent of lithium, and the mole percent of lithium in the coating is greater than the mole percent of lithium in the substrate.

2. The substrate according to claim 1, wherein the nickel in the substrate is nickel element, nickel oxide, nickel alloy, or any combination thereof.

3. The substrate according to claim 2, wherein the substrate contains the element nickel.

4. The substrate according to claim 2, wherein the substrate includes a nickel alloy.

5. The substrate according to claim 4, wherein the nickel alloy includes aluminum, iron, copper, molybdenum, chromium, titanium, cobalt, tungsten, or any combination thereof.

6. The substrate according to any one of claims 1 to 5, wherein the substrate is a plate, a foam, or a mesh.

7. The substrate according to claim 6, wherein the substrate is a plate.

8. The substrate according to claim 7, wherein the plate has a thickness of about 1 μm to about 10,000 μm.

9. The substrate according to claim 7 or claim 8, wherein the plate has an apparent porosity of less than about 5%.

10. The substrate according to claim 6, wherein the substrate is a foam.

11. The substrate according to claim 10, wherein the foam has a thickness of about 1 μm to about 5,000 μm.

12. The substrate according to claim 10 or claim 11, wherein the foam has an apparent porosity of more than about 5%.

13. The substrate according to claim 12, wherein the foam has an apparent porosity of more than about 50%.

14. The substrate according to claim 6, wherein the substrate is a mesh.

15. The substrate according to claim 14, wherein the mesh has a thickness of about 1 μm to about 5,000 μm.

16. The substrate according to claim 14 or claim 15, wherein the mesh has an apparent porosity of more than approximately 5%.

17. The substrate according to claim 16, wherein the mesh has an apparent porosity of more than approximately 50%.

18. The substrate has a density of approximately 0.01 g / cm³. 2 ~Approx. 14.0g / cm 2 A substrate according to any one of claims 1 to 17, having the weight-to-area ratio.

19. The substrate has a density of approximately 0.1 g / cm³. 2 ~Approx. 0.5g / cm 2 A substrate according to any one of claims 1 to 18, having the weight-to-area ratio.

20. The substrate has a density of approximately 0.1 g / cm³. 2 ~Approx. 0.2g / cm 2 A substrate according to any one of claims 1 to 19, having the weight-to-area ratio.

21. The substrate according to any one of claims 1 to 20, wherein the coating has a thickness of about 1 nm to about 100 μm.

22. The substrate according to any one of claims 1 to 21, wherein the coating has a thickness of about 1 nm to about 1 μm.

23. The substrate according to any one of claims 1 to 22, wherein the coating comprises lithium element, lithium peroxide, lithium hydroxide, lithium oxide, lithium carbonate, lithium alloy, or any combination thereof.

24. The substrate according to any one of claims 1 to 23, wherein the coating includes at least one knot extending away from the first surface of the substrate.

25. The substrate according to claim 24, wherein the at least one node comprises aluminum, silicon, magnesium, calcium, oxygen, or any combination thereof.

26. The substrate is the substrate according to any one of claims 1 to 25, wherein the substrate contains less than about 0.5 mole percent of lithium.

27. The substrate is a substrate according to any one of claims 1 to 26, wherein the substrate does not contain lithium.

28. The substrate according to any one of claims 1 to 27, wherein the coating comprises at least about 5 mole percent lithium.

29. The substrate according to any one of claims 1 to 28, wherein the coating is at least partially disposed on at least one of the second surface and the outer surface of the substrate.

30. A method for forming a setter body for sintering a solid electrolyte material, wherein the method is: (a) Placing a substrate in a heating chamber, wherein the substrate has a first surface, a second surface opposite to the first surface, and an outer surface extending from the first surface to the second surface, and the substrate contains nickel, (b) Providing a lithium source in the heating chamber, (c) The method comprising heating the heating chamber to a temperature of about 600°C to about 1,500°C to form a coating on the first surface of the substrate that contains lithium from the lithium source at least partially, thereby forming the setter body.

31. The method according to claim 30, wherein the nickel in the substrate is nickel element, nickel oxide, nickel alloy, or any combination thereof.

32. The method according to claim 31, wherein the substrate contains nickel.

33. The method according to claim 31, wherein the substrate includes a nickel alloy.

34. The method according to claim 33, wherein the nickel alloy includes aluminum, iron, copper, molybdenum, chromium, titanium, cobalt, tungsten, or any combination thereof.

35. The method according to any one of claims 30 to 34, wherein the substrate is a plate, a foam, or a mesh.

36. The method according to any one of claims 30 to 35, wherein the lithium source comprises lithium lanthanum zirconium oxide (LLZO).

37. The method according to claim 36, wherein the LLZO is doped.

38. The method according to claim 36, wherein the LLZO is undoped.

39. The method according to any one of claims 30 to 38, wherein the substrate contains less than about 0.5 mole percent of lithium.

40. The method according to any one of claims 30 to 39, wherein the substrate does not contain lithium.

41. The method according to any one of claims 30 to 40, wherein the coating comprises at least about 1 mole percent of lithium.

42. The method according to any one of claims 30 to 41, wherein the coating comprises at least about 5 mole percent of lithium.

43. The method according to any one of claims 30 to 42, wherein the coating is at least partially disposed on at least one of the second surface and the outer surface of the substrate.

44. The method described above is (d) The method according to any one of claims 30 to 43, further comprising flowing a gas into the heating chamber.

45. The method according to claim 44, wherein the gas comprises a mixture of hydrogen and an inert gas.

46. The method according to claims 44 and 45, wherein the gas is introduced into the heating chamber at a flow rate of approximately 1 SCCM to approximately 3,000 SCCM.

47. The method according to any one of claims 44 to 46, wherein step (d) is carried out at least partially during step (c).

48. The method according to any one of claims 30 to 47, wherein the atmosphere inside the heating chamber during step (c) includes carbon monoxide, carbon dioxide, ammonia, hydrogen sulfide, methane, hydrogen, nitrogen, argon, helium, or any combination thereof.

49. The method described above is (e) The method according to any one of claims 30 to 48, further comprising repeating step (c).

50. The lithium source is a first lithium source, and the method is (e-1) After step (c), replace the first lithium source in the heating chamber with a second lithium source, and (e-2) The method according to claim 49, further comprising repeating step (c).

51. The method according to claim 50, further comprising cooling the heating chamber before step (e-1).

52. A method for forming a sintered solid electrolyte material, wherein the method is (dd) Placing the setter body according to any one of claims 1 to 29 in the heating chamber, (ee) Placing a green body on the coating of the setter body, wherein the green body includes a solid electrolyte material, (ff) The heating chamber is heated to a temperature of approximately 600°C to approximately 1,500°C to form the sintered solid electrolyte, The method wherein the solid electrolyte material loses less than about 20 mole percent of lithium in step (cc).

53. The method according to claim 52, wherein the solid electrolyte material loses less than about 15 mole percent of lithium during the step (cc).

54. The method according to claim 52, wherein the solid electrolyte material loses less than about 10 mole percent of lithium during the step (cc).

55. The method described above is (gg) The method according to any one of claims 52 to 54, further comprising flowing gas into the heating chamber.

56. The method according to claim 55, wherein the gas comprises a mixture of hydrogen and an inert gas.

57. The method according to claims 55 and 56, wherein the gas is introduced into the heating chamber at a flow rate of approximately 1 SCCM to approximately 3,000 SCCM.

58. The method according to any one of claims 55 to 57, wherein step (dd) is carried out at least partially during step (cc).

59. The method according to any one of claims 52 to 58, wherein the atmosphere inside the heating chamber during step (cc) includes carbon monoxide, carbon dioxide, ammonia, hydrogen sulfide, methane, hydrogen, nitrogen, argon, helium, or any combination thereof.

60. The method according to any one of claims 52 to 59, wherein the atmospheric pressure inside the heating chamber during step (cc) is about 1 Pa to about 10 MPa.

61. The green body further comprises at least one of a pore-forming agent and a binder, and step (cc) is (cc-1) Heating the heating chamber to a first temperature of about 400°C to about 800°C to burn at least one of the pore-forming agent and the binder, and (cc-2) The method according to claim 52, further comprising heating the heating chamber to a second temperature of about 600°C to about 1,500°C to form the sintered solid electrolyte, wherein the second temperature is higher than the first temperature.

62. The aforementioned method, The method according to claim 61, further comprising introducing (dd) gas into the heating chamber.

63. The step (dd) is (dd-1) During step (cc-1), at least partially, the first gas is introduced into the heating chamber, and The method according to claim 62, further comprising (dd-2) introducing at least partially a second gas into the heating chamber during step (cc-2).

64. The method according to claim 63, wherein the first and second gases are each independently introduced into the heating chamber at a flow rate of approximately 1 SCCM to approximately 3,000 SCCM.

65. The method according to claim 63 or claim 64, wherein the first gas comprises oxygen or air, and the second gas comprises a mixture of hydrogen and an inert gas.